Fabrication and application of carbon sequestration grouting material for sealing leakages in mine strata - Jing Mei; Jianwei Cheng; Shuping Sheng; Yejiao Liu; Zhiyuan Ma; Qiang Fu; Dezhi Ran (European Journal of Environmental and Civil Engineering, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Tamarind seed polysaccharide governs the structure and function relationship in retrograded starch complexes: Modulation of molecular order, network stability, and digestibility - Zijun Xi; Haotian Yin; Jiani Liu; Qing Gong; Junjie Yi; Hang Ma; Ran Wu; Xueming Xu; Yongshuai Ma (Food Hydrocolloids, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Where are the retention hotspots of microplastic particles in the riverbed with complex topography - Haiyu Yuan; Guangqiu Jin; Kaiwen Zhang; Xue Ping; Ran Ma; Guiqiao Wang; Xiangfei Qi; Hanqing Zhao (Journal of Hydrology, 2026)

Engineering interface-conﬁned Pt-Ce nanostructures on alumina towards efficient diesel soot oxidation - Baofang Jin; Yuan Gao; Shuang Liu; Yue Ma; Rui Ran; Duan Weng; Xiaodong Wu (Journal of Environmental Chemical Engineering, 2026)

Al-modified ReS2/TiO2 with enhanced adsorption and stepwise interfacial charge migration for photocatalytic PFOA removal - Ran Chen; Feng Liu; Zhenkai Liu; Jun Wan; Qidi Liu; Yixin Ma; Yan Li; Shunli Wan; Yongming Luo; Haijiao Xie (Journal of Environmental Chemical Engineering, 2026)

Elucidating time-resolved salt stress response mode of salt-tolerant microalgae under simulated seawater salinity: Molecular strategies for algal cultivation and bioproducts production - Meng Ma; Bing Guo; Xinhao Gao; Ran Li; Zichao Zhao; Tao Sun; Li Yao (Journal of Environmental Chemical Engineering, 2026)

Effects of ethers on CO2 capture performance and phase change behavior of DBU-EG system: Hydrogen bonding and polarity - Menghan Yuan; Zili Fan; Yutong Wang; Jiangnan Ran; Xiaotian Ma; Xinming Zhou; Xiang Feng; Hui Fu (Chemical Engineering Journal, 2026)

Application of 3D printing technology in the development of future foods derived from edible fungi: From the perspective of creating dysphagia diets based on multidimensional quality differences of various shiitake mushrooms - Caoyu Li; Xinyi Zhao; Ran Zhang; Ruotong Bao; Qiuhui Hu; Yuxi Zhang; Gaoxing Ma; Rui Weng (Food Research International, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Making waves: Harnessing the disinfection byproduct chlorite as an oxidant precursor for micropollutant abatement - Xi Zhang; Yimeng Ma; Mingkai Jia; Wanxin Li; Jiarui Han; Rihui Li; Xin Yang; Ran Yin; Hongqiang Ren (Water Research, 2026)

Trypanosoma evansi extracellular vesicles suppress lipopolysaccharide-induced pro-inflammatory responses through host Src homology 2 domain-containing protein tyrosine phosphatase 1 activation - Ran Wei; Shikai Song; Man Zhang; Rui Chen; Huixia Zhang; Sisi Ma; Song Wang (Veterinary Parasitology, 2026)

Reductive degradation of bromate in drinking water by far-UVC photolysis of sulfite - Zhengyang Wang; Xi Zhang; Yimeng Ma; Ran Yin; Jing Zhao (Journal of Hazardous Materials, 2026)

The tautomerism induced by the number of hydroxyl groups in COFs and its contribution to thorium adsorption - Shangjie Zhao; Long Chen; Xiaofan Ding; Ke Wang; Jicong Li; Ran Zhang; Jing Zhao; Ke Ma; Jinping Liu; Songtao Xiao (Journal of Environmental Sciences, 2026)

Mechanistic insights into the thermal oxidative degradation of waste wind turbine blades: Thermokinetics and ReaxFF MD simulations - Guoqing Huang; Chuan Ma; Xin Huang; Yunlin Shao; Jingyu Ran (Chemical Engineering Journal, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

Area and Growth Contributions to Dynamics of Forest Biomass Carbon Stocks in Northeast China - Chunhua Zhang; Yue Cao; Ran Wang; Wei He; Haoran Man; Jie Ma; Dan Lu; Shoujian Zhang (Chinese Geographical Science, 2026)

Aboveground inputs rather than belowground root drive SOC responses to long term N addition in alpine grassland ecosystems of Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Juejie Yang; Ying Li; Yaoming Li; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; et al. (Agriculture, Ecosystems & Environment, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Membrane separation technology in hydrometallurgy: Recent advances, innovative applications, and sustainable resource recovery - Ran An; Baozhong Ma; Zhihe Cao; Yubo Liu; Xiang Li; Yongqiang Chen; Chengyan Wang (Process Safety and Environmental Protection, 2026)

The impact on greenhouse gas emissions of damming the rivers in China from 1960 to 2060 - Xincong Liu; Ran Fang; Yaqin Jiang; Shan Chen; Xiehang Chen; Hengyu Pan; Hongqiao Chen; Qiang Ma; Li Zeng (Journal of Cleaner Production, 2026)

Eccentricity forcing of late Paleogene dust accumulation in the western USA across the Eocene-Oligocene transition - Xiangwei Guo; Majie Fan; Yiquan Ma; Steven L. Forman; Dennis O. Terry; Ran Feng (Global and Planetary Change, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

A fast estimation method for pulsar signal period based on point cloudization of photon arrival times - Shuo Zhang; Xin Ma; Wenjia Zhang; Tianhao Xie; Shanchuan Ran; Peiling Cui; Xiaolin Ning (Advances in Space Research, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Hyphomicrobiales-mediated C–S coupling underpins enantiomeric differences in soil nutrient cycling induced by the chiral herbicide napropamide - Yuying Wang; Ran Wu; Shijie Cui; Qinghua Ma; Yanzhe Dong; Xintong Li; Lukuan Huang; Yaxin Zhu; Miaozhen Cai; Shaoting Du (Journal of Hazardous Materials, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Construction of Cu-SSZ-13@SAPO-34 selective catalytic reduction catalyst: Multifunctional protective shell against hydrothermal aging and chemical poisoning - Yang Gao; Yue Ma; Letong Yang; Xiaodong Wu; Rui Ran; Yanyang Yu; Duan Weng (Fuel, 2026)

Synergistic effects of nitrification inhibitor and ABA-producing Bacteria on cadmium mitigation and quality improvement in Pak choi - Haoqi Cui; Qinghua Ma; Xiaohang Sun; Shumeng Fu; Chengzhi Liu; Lukuan Huang; Ran Wu; Yaxin Zhu; Shaoting Du (Food Chemistry, 2026)

The saturation degree of dietary fatty acids alters the phenotypes of lipoprotein subclasses and plasma metabolome in piglets - Ying Li; Yajie Wang; Ran Ma; Zhihua Li; Zemeng Feng; Xiangfeng Kong; Qian Zhou; Xiaoming Guo; Yulong Yin; Yongning Wu; Qinghua He (Food Chemistry, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Mechanical Deterioration and Crack Propagation Characteristics of Mudstone Under Cyclic Loading: Insights from Acoustic Emission Fractal Analysis - Qican Ran; Yunpei Liang; Chunfeng Ye; Xiao Song; Tengfei Ma; Zihan Chen (Rock Mechanics and Rock Engineering, 2026)

Role and therapeutic potential of icariin in metabolic diseases - Anni Song; Ran Wei; Yang Yang; Haoshuang Li; Fengyi Chen; Yutong Pang; Xiaotong Ma; Shijie Hao (Inflammopharmacology, 2026)

Characteristics and possible genesis of potassium in deep-buried brine in the Northern Dongying Depression - Xiaosan Yang; Wenquan Li; Shuai Wang; Lina Zhao; Yuhua Li; Weihong Yang; Dongchao Ren; Qiao Chen; Yibo Zhang; Ran Ma (Carbonates and Evaporites, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Molecular Recalcitrance Govern Natural Organic Matter Stabilization on Clay Minerals Versus Interfacial Reactions on Iron Oxides - Ran Zhang; Cuiyun Niu; Wanli Lian; Haiyu Yuan; Yali Chen; Jie Ma; Huike Ye; Xiaojing Li; Liping Weng (Applied Clay Science, 2026)

HSP72 alleviates heat stress-induced oxidative damage in boar Sertoli cells through modulating the AGE-RAGE/NOX4/NF-κB axis - Qianqian Jiang; Jing Yang; Jiajia Ma; Ning Gao; Bo Weng; Maoliang Ran (Animal Reproduction Science, 2026)

TangShenKang decoction plays an anti-inflammatory and anti-fibrotic role in diabetic nephropathy by activating AT2R/ATIP1/SHP1 axis and antagonizing angiotensin II - Ran Wei; Jian Ma; Zeyu Yu; Wei Zou; Na Zhao (Molecular and Cellular Biochemistry, 2026)

Dose- and time-dependent cardioprotection of liproxstatin-1 via sequential modulation of ferroptosis pathways after myocardial ischemia-reperfusion - Ziwei Huang; Xixi Chen; Junyi Ren; Linlin Wan; Miao Li; Xiaowu Ma; Jing Dong; Hong Ran (Molecular and Cellular Biochemistry, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Soil water vapor adsorption and condensation governed by groundwater depth and vadose zone lithology in arid and semi-arid regions - Ran Li; Haibo Feng; Yanhong Xue; Jianwei Zhou; Lei Fang; Danhui Su; Xiaoming Zheng; Siqi Tan; Huyuan Zheng; Yongxiang Ma (Journal of Hydrology, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Revealing the NO oxidation mechanism by the Ce-doped LaCoO3 perovskite catalysts - Ran Ao; Xiujuan Yang; Tao Pu; Quxiu Dai; Jie Yang; Longgui Xie; Zhiying Guo; Liping Ma; Haijiao Xie (Fuel, 2026)

UV-328 disrupts mineral nutrient homeostasis and secondary metabolism in Arabidopsis thaliana: Linking physiological responses to molecular mechanisms - Ying Wang; Yaxin Zhu; Xintong Li; Qinghua Ma; Lukuan Huang; Ran Wu; Miaozhen Cai; Shaoting Du (Environmental Pollution, 2026)

An intelligent multi-stage fishway integrating computer vision and adaptive hydraulic control - Guiwen Rong; Tengyu Ma; Hongling Jiang; Shangzhi Chen; Yangyan Zhang; Guoqing Zhao; Hai Lin; Huaiqin Ran (Ecological Engineering, 2026)

Electrolyte-driven H₂O₂ boost in plasma activated water: The role of sulfate in plasma electrolysis - Tailin Ren; Kun Liu; Congfu Ran; Xiangyu Ma; Jianan Zhao; Renwu Zhou; Patrick J. Cullen (Chemical Engineering Journal, 2026)

Paeoniae Radix Alba polysaccharides: Structural characterization, macrophage immunomodulation, and potent vaccine adjuvant activity - Ming Zhao; Yushi Wang; Ran Guan; Shiyue Qin; Guoqiu Li; Jiaqi Wang; Zhiye Wang; Junyan Shang; Lingyi Xu; Qingrui Lin; Yanxia Ding; Xiaodan Ma; et al. (Carbohydrate Polymers, 2026)

Experimental Investigation on the Mixed-Mode I–II Fracture Behavior in Layered Shale - Tianshou Ma; Zexin He; Haonan Wang; Yang Liu; Ran Xu; Yi Wang (Rock Mechanics and Rock Engineering, 2026)

Exploring the spatiotemporal variability of leaf area index and its influence on land surface temperature: A city-scale analysis in Hong Kong - Chaoran Zhang; Ran Chen; Xingcheng Lu; Frankie Kwan Kit Wong; Wenkai Li; Kai Cheng; Qin Ma; Yuan Xu; Tung Fung; Qinghua Guo (Urban Forestry & Urban Greening, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Near-surface ground ice map of the Northern Hemisphere - Bingquan Wang; Youhua Ran; Xin Li; Jan Hjort; Olli Karjalainen; Qingbai Wu; Yu Sheng; Huijun Jin; Defu Zou; Lin Zhao; Rui Ma; Ziyong Sun; et al. (Science Bulletin, 2026)

Embryonic Proto-Tethys Ocean: Evidence from the early Ediacaran Kuyake ophiolite mélange along the Altyn Tagh in NW China - Hong-Ran Wang; Chuan-Lin Zhang; Hua-Dong Ma; Yan Jing; Masumeh Sargazi; Zhi-Hao Song (Precambrian Research, 2026)

Unravelling the synergy in catalytic debromination over transition bimetals: d-orbital reconfiguration and electronic structure regulation - Zhi He; Chuan Ma; Xin Huang; Yunlin Shao; Jingyu Ran (Journal of Environmental Chemical Engineering, 2026)

A comprehensive review of emerging protein modification methods: modified properties and potential applications - Hao Zhu; Kaifang Guan; Xiaolin Liu; Ran Xiao; Ying Ma; Weihong Lu; Xue Han; Rongchu Wang; Tianjiao Niu (Food Chemistry, 2026)

Energy–vortex–momentum coupling bridges hydrodynamics and mass transfer of perfluoroalkyl acids - Yixin Ma; Zulin Hua; Limei Zhong; Shunli Wan; Yan Li; Ran Chen; Qidi Liu (Environmental Pollution, 2026)

Cross-scale modeling of bacteria-contaminant spatiotemporal dynamics in 3D bioprinted hydrogel for dye biodegradation - Weihao Guo; Ya-Nan Hou; Wei Xing; Ran Xu; Jinfeng Ma; Ai-Jie Wang; Nanqi Ren; Cong Huang (Bioresource Technology, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

An improved ion-exchange-to-silver-salt procedure for δ18O measurement of nitrate in natural samples - Bo Wang; Chao Li; Ying Wang; Linbao Chen; Yuting Wang; Ran Ma; Zhengyu Zhu; Youping Zhou (Analytica Chimica Acta, 2026)

Risk assessment, resistance monitoring and mechanism of field-evolved resistance to broflanilide in the tobacco cutworm, Spodoptera litura - Xiao Guo; Yilu Tong; Ren Li; Shengran Zhang; Daofeng Zhang; Cheng Qu; Xiaoli Ma; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Enhanced polystyrene nanoplastic removal by CTAB-modified magnetic biochar: Adsorption performance and mechanisms - Longwei Fu; Ruili Gao; Bin Xue; Ran Duan; Kun Ma; Lin Chen; Biao Jia (Journal of Environmental Management, 2026)

Knowledge-data-model-driven multimodal few-shot learning for hyperspectral fine classification: Generalization across sensor, category and scene - Qiqi Zhu; Mingzhen Xu; Rui Ma; Longli Ran; Jiayao Xue; Qingfeng Guan (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

H₂-rich syngas from synergistic steam gasification of biomass with spent LIB cathodes: Catalytic kinetics and metal recovery - Ran Jiao; Lijie Sun; Bowen Li; Xinran Zhou; Yifei Xu; Yu Chen; Fenglei Qi; Xiaohao Liu; Rui Diao; Zhenting Zha; Peiyong Ma (Chemical Engineering Journal, 2026)

Discovery of 5-fluoro-aminopyrimidine derivatives as dual BTK/FLT3 inhibitors for the treatment of rheumatoid arthritis - Fansheng Ran; Yifan Ma; Tiantian Sun; Liujie Ji; Qinyan Cai; Yanan Zhang; Yong Ling; Chunlin Zhuang (Molecular Diversity, 2026)

Boosting coalbed methane recovery through nanofluid-mediated pore and interfacial regulation - Jiajia Zhao; Shixiang Tian; Yihong Wen; Ting Liu; Tong Liu; Xuan Zhang; Tengfei Ma; Qican Ran (Process Safety and Environmental Protection, 2026)

Attributing changes in evapotranspiration and runoff across the continental U.S. using the Budyko hypothesis combined with the Shuttleworth-Wallace model - Ran Lv; Shanlei Sun; Zaoying Bi; Yi Liu; Qianrong Ma; Yongjian Ren; Lingna Wei; Yang Zhou; Botao Zhou (Journal of Hydrology, 2026)

Covalent triazine frameworks as adsorbent for oxytetracycline and ciprofloxacin removal: Mechanism and DFT calculation - Wenwen Zhang; Guangyang Wang; Xinyi Zhang; Yufei Hui; Zhining Zhong; Wenlong Zhang; Ran Ma; Hongjie Wang (Journal of Environmental Chemical Engineering, 2026)

Contribution of herbaceous energy crops in maintaining runoff and reducing soil loss on the loess slopes under natural rainfall in the semi-arid area - Ran Huai; Lingchao Meng; Tianni Cheng; Yingge Xie; Yulei Ma; Zhihua Shi; Gao-Lin Wu (CATENA, 2026)

Pretreatment sequence of torrefaction and leaching for high–alkali biomass valorization: Focus on elemental migration, mineral evolution, carbon structure and torrefaction mechanism - Bowen Li; Junling Du; Rui Diao; Xu Hu; Cunzhang Yang; Ran Jiao; Fenglei Qi; Zhenting Zha; Xiaohao Liu; Peiyong Ma (Bioresource Technology, 2026)

Characterizing low-supersaturation CCN activity with AAC-CCNC system at a mountain site in continental region in China - Mengyao An; Jiangchuan Tao; Yaqing Zhou; Minghua Liang; Li Li; Juan Hong; Linhong Xie; Weikang Ran; Shaobin Zhang; Qiaoqiao Wang; Qiyuan Wang; Nan Ma (Atmospheric Research, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

Phage-cocktail-based biocontrol of multidrug-resistant Klebsiella pneumoniae both in vitro and in vivo - Ling Zou; Yang Yu; Dongxue Yue; Chuanxu Wang; Shijie Xu; Wenhua Liu; Shouzhen Xu; Jing Ma; Hong-Bo Ni; Tao He; Ran Wang; Yehui Sun; et al. (Archives of Virology, 2026)

Low N Deposition Coupled With Climate Warming Promote Soil Asymbiotic N Fixation via Increasing Microbial Specialists in Alpine Grassland - Ke Zhang; Yaoming Li; Ran Zhang; Anna Du; Zuyan Ma; Hang Shi; Juejie Yang; Wenli Ding; Hao Shen; Richard D. Bardgett; Huaiying Yao; Shikui Dong (Global Change Biology, 2026)
Biological nitrogen fixation (BNF) is a vital process for introducing new N into natural ecosystems, and this process has been demonstrated to be suppressed by high N deposition. However, the net ecological effect and underlying mechanisms of BNF under chronic low‐level N deposition, characteristic of terrestrial ecosystems, remain highly uncertain. Given that climate warming is a key environmental change factor concurrent with N deposition, it is important to investigate whether climate warming can change BNF activity and alter the effects of N deposition on BNF. To fill these knowledge gaps, we implemented a decade‐long‐term manipulation experiment in an alpine grassland ecosystem with 5 treatments, that is, experimental warming (W), low‐level N deposition (N L ), high‐level N deposition (N H ), combination of climate warming and low‐level N deposition (WN L ) and the control (CK). BNF rate was measured by 15 N 2 isotope discrimination. We found that N L significantly stimulated BNF by 112%, contrasting sharply with the complete suppression under N H . Climate warming alone increased the BNF rate by 123%, while the WN L amplified this effect, stimulating BNF by 234%. Structural equation modeling revealed that WN L selectively favored specific diazotrophic groups ( Desulfovibrio ), whose proliferation directly drove the observed BNF shifts. In this N‐limited alpine grassland, low‐level chronic N deposition, especially when combined with warming, fundamentally shifts the diazotrophic community structure by driving a process of niche contraction. This selection process functionally enriches specialized diazotrophs, resulting in a dramatic, positive feedback that significantly promotes the overall biological nitrogen input. Our findings highlight the potential for increased N inputs under realistic future climate scenarios and provide a scientific basis for precision N management in alpine grasslands, both on the Qinghai‐Tibetan Plateau and worldwide.

Microplastic exposure reshapes the virome and virus–bacteria networks with implications for immune regulation in Mytilus coruscus - Jingyan Zhang; Xiaoya Wang; Qingyang Li; Bin Li; Haiping Ma; Shijie Wang; Qianwen Ying; Suzhen Ran; Ekaterina O. Leonteva; Mikhail B. Shilin; Yingying Ye; Xiangli Dong; et al. (Marine Pollution Bulletin, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Membrane-targeted molecular binding and redox collapse underlie UV-328 toxicity in Chlorella pyrenoidosa - Lukuan Huang; Siyu Zhang; Qinghua Ma; Shumeng Fu; Danyang Zou; Yaxin Zhu; Ran Wu; Shaoting Du (Journal of Hazardous Materials, 2026)

Geographical and seasonal dynamics of nutritional and functional profiles in Maiwa yak milk from the Qinghai-Tibetan Plateau - Yanshi Jiang; Rongmei Liu; Xiaolin Liu; Ran Xiao; Weihong Lu; Tianjiao Niu; Ying Ma; Kaifang Guan; Rongchu Wang (International Dairy Journal, 2026)

Role of Ni-Co bimetals in CaCr2O4 catalysts for dry reforming of methane: Promotion in coke resistance - Jie Gao; Hangjia Zhang; Jingyu Ran; Chuan Ma; Xin Huang; Yunlin Shao; Huayu Qiu; Zhiliang Ou; Lei Tang (Fuel, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Identification of quantitative trait loci qPL6 for petiole length in soybean - Weiwei Fan; Lindong Wang; Wenxuan Huang; Jia Liu; Bing Li; Jingyu Peng; Ruirui Ma; Ran Xu; Lianjun Sun (Theoretical and Applied Genetics, 2026)

Cntn4 Gene Deficiency Promotes Autism-Like Phenotypes Associated with Gut Microbiota Perturbations and Gut-Brain Axis Metabolomic Alterations in Mice - Mingxian Wang; Zhiyuan Liang; Hongbin Zhuang; Xueshan Cao; Guanwei Ma; Yuan Sun; Xi Yan; Xiaoqian Ran; Hailing Guan; Liming Shen (Molecular Neurobiology, 2026)

Effects of chronic social defeat stress on behavior and cognition by activating the ERS-NLRP3 signaling pathway in adult mice - XiaoLei Gao; Ran Hao; ZengYun Jing; GuangBiao Huang; Lina Wang; Anna Ma; ZhaoHui Zhang; Tong Zhao (Metabolic Brain Disease, 2025)

Development and Application of Respiratory Pseudovirus Packaging System - Jingwen Fu; Ran Chen; Shihuan Zhong; Han Jiang; Jiayue Yang; Xuezheng Ma; Chenze Lu (Aerosol Science and Engineering, 2025)

A two-stage ship path planning method based on trial maneuvers - Yangyu Zhou; Shuxiu Liang; Qiaofeng Ma; Qingren Xue; Jia Li; Ziyu Deng; Ran Yan (Ocean Engineering, 2025)

Three-dimensional trajectory tracking of autonomous underwater vehicles via neural network learning finite time adaptive robust control - Linyuan Guo; Ran Zhou; Ze Wang; Qingchang Guo; Liran Ma; Chuxiong Hu; Jianbin Luo (Ocean Engineering, 2025)

Effects of dietary cinnamic acid supplementation on growth performance, meat quality, muscle development and antioxidant capacity of Yuedong black pigs - Zewei Ma; Shuai Liu; Ran Yi; Jinhao Liu; Canjun Zhu; Songbo Wang; Lina Wang; Gang Shu; Qingyan Jiang; Ruifan Wu (Meat Science, 2025)

Enhanced ofloxacin degradation by three-dimensional electrochemical activation of peroxymonosulfate using nano ZVC doped reed straw biochar particle electrode - Wenwen Zhang; Jiahui Bi; Yufei Hui; Guangyang Wang; Ran Ma; Hongjie Wang (Journal of Environmental Chemical Engineering, 2025)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

Rational screening of anti-E. coli peptides via GAT-MD integration leveraging foodborne antimicrobial sequence features - Qiqi Wang; Qiang Ma; Shiqi Chen; Ke Han; Huicong Wu; Zhiyue Feng; Qian Ran; Jiankang Ren; Xiaomei Wang; Boyan Sun; Haiyang Jiang (Food Chemistry, 2025)

Effect of electron beam irradiation on physicochemical and protein properties of scallop adductor muscles during cold storage - Zhupeng Zhang; Peng Ge; Chaoqi Han; Fan Zhang; Wenxiu Wang; Ran Suo; Qianyun Ma; Zhenzhen Wang; Jianfeng Sun (Food Chemistry, 2025)

Novel anti-obesity mechanisms of Pleurotus eryngii: Based on the regulatory effects of potential key gut microbiota and associated metabolites - Yaning Duan; Yunyan Yu; Hongshan Pan; Ruotong Bao; Ran Zhang; Qiuhui Hu; Gaoxing Ma (Food Bioscience, 2025)

The effect of degree of esterification of pectin on the grainy properties of post-heated fermented milk - Fei Gao; XueYing Mao; Pengjie Wang; Ran Wang; Hongliang Li; Hairan Ma; Chong Chen; Sijia Song; Dongdong Li (Food Hydrocolloids, 2025)

Comprehensive physiological, transcriptomic, and metabolomic analyses reveal that preservation paper treatment mediates the AsA-GSH cycle and energy metabolism pathways to delay the ageing mechanism of Pleurotus ostreatus - Zhi Yan; Lingshuai Meng; Huaituo Yang; Donglei Zhang; Lulu Ran; Chao Ma (Food Packaging and Shelf Life, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

Dolomite reservoir differences in characteristics and controlling factors of grainstone shoal facies in Qixia Formation, Sichuan Basin - Benjian Zhang; Hualing Ma; Xiaojie Huang; Xihua Zhang; Xiao Chen; Fujie Jiang; Chen Xie; Yangui Chen; Ran Liu; Wei Wang; Haitao Sun (Carbonates and Evaporites, 2025)

Deep learning-based inversion of stress curves and crack quantification in NPR anchored rock masses - Li Cui; Wenfeng Ren; Chengyu Miao; Yong Zhang; Chengwei Zhao; Sheng-tian Zhai; Ran Hai; Jianjun Ma; Xiaoming Sun (Journal of Mountain Science, 2025)

A multi-dimensional comparative study of 505(b)(2) NDAs approved by FDA and Class 2 NDAs approved by NMPA from 2017 to 2023: Uncovering trends, characteristics, and regulation of modified new drugs - Lixia Fu; Songtao Dong; Ran Xie; Guoshu Jia; Nan Zhao; Qian Xiang; Xiwei Ji; Xia Zhao; Xiaoyuan Chen; Lingyue Ma; Yimin Cui (Regulatory Toxicology and Pharmacology, 2025)

Regulation of phytoplankton community by mesoscale eddies and the East Indian Coastal Current in the southwestern Bay of Bengal during the northeast monsoon - Hao Chen; Yuanli Zhu; Lihua Ran; Mengjia Zhang; Xiao Ma; Hongliang Li; Feng Zhou; W.N.C. Priyadarshani; Zhibing Jiang (Marine Environmental Research, 2025)

Seasonal mercury in an endangered primate from fragmented karst forest: Does behavioral observation advance ecotoxicological risk assessment? - Ran Huang; Haili Chen; Qiuyan Guo; Meijing Lu; Shijun Wu; Dengpan Nong; Chan Li; Yanju Ma; Qihai Zhou (Journal of Hazardous Materials, 2025)

Tea saponin assisted micellar extraction combined with in-situ aqueous two phase enrichment of flavonoids and lactones from functional food - Si-Yi Liu; Xin-Ran Ma; Qian-Xue Shen; Huang-Fei Jin; Jun Cao (Food Research International, 2025)

Effect of cooking condiments on swelling and starch-gluten matrix structural/molecular changes of cooked noodles - Wenxin Xie; Peng Wang; Ran Zhao; Kexin Shi; Meng Ma; Yanfei Wang; Qingjie Sun; Man Li; Fengwei Xie (Food Chemistry, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Theoretical Analysis and Engineering Application of the Interaction Between NPR Anchor Cable and Deep Surrounding Rock Considering Intermediate Principal Stress - Li Cui; Xiaoming Sun; Ran Hai; Jianjun Ma; Chaosheng Wang (Rock Mechanics and Rock Engineering, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Molecular characteristics of clays selectively binding with biomass-burning smoke-derived dissolved organic matters and their interaction with tetracycline adsorption - Weifeng Chen; Huiying Zhang; Yinhua Zhong; Jinzhi Ni; Ran Wei; Yanbin Ma; Zhichong Qi (Journal of Environmental Chemical Engineering, 2025)

Room-temperature trimethylamine gas sensor with enhanced performance using biomass-derived carbon quantum dot modified biochar - Mengyuan Liu; Bo Ran; Ping Hu; Jialu Fang; Jun Sun; Yuqing Bai; Qingshan Ma; Xiaoman Ma; Zhaofeng Wu; Haiming Duan (Journal of Environmental Chemical Engineering, 2025)

Framework Al density determines linearly the low-temperature SCR activity of Cu-SSZ-13 via promoting [Cu(NH3)2]+ dimeric re-oxidation - Yue Ma; Songqi Cheng; Letong Yang; Ziyao Chen; Xiaodong Wu; Liping Liu; Yang Gao; Xiangju Meng; Rui Ran; Jianbo Liu; Duan Weng (Journal of Environmental Chemical Engineering, 2025)

Unraveling the surface and interface reaction mechanisms of CO2 hydrogenation to methanol over Ga-modified Cu-based catalysts: Insights from DFT calculations - Jie Gao; Hangjia Zhang; Jingyu Ran; Guohua Sang; Zhiliang Ou; Lei Tang; Huayu Qiu; Yunlin Shao; Chuan Ma; Xin Huang (Journal of Environmental Chemical Engineering, 2025)

Exploring the role of oxygen species in calcium-modified steel slag for CO2 capture during sludge gasification - Longgui Xie; Yuetao Luo; Qihong Cen; Binbin He; Wang Du; Xia Yin; Zhiying Guo; Xiaofeng Huang; Quxiu Dai; Nanqi Ren; Liping Ma; Jie Yang; et al. (Chemical Engineering Journal, 2025)

Metal–organic framework (MOF)-based biosensors for monitoring pathogens in public health - Shupei Yin; Kang Mao; Wei Ma; Junxia Su; Guili Yang; Jiabing Ran; Changying Yang; Hua Zhang (Chemical Engineering Journal, 2025)

Grazing mediates soil nutrient stocks through changing the plant functional composition and plant biomass allocation in alpine grassland - Fengcai He; Shikui Dong; Chunhui Ma; Xinghai Hao; Hao Shen; Juejie Yang; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Association between brain connectivity and renal pathophysiology: a multi-trait Mendelian randomization analysis - Zihui Xu; Manyu Ma; Ran An; Yanqing Wang (Brain Structure and Function, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Bioremediation strategies for hexavalent chromium: Development and safety assessment of recombinant Escherichia coli strain 3458 - Yeting Weng; Qiuying An; Dongbei Guo; Ningjing Gan; Weijie Zeng; Wanting You; Zhangye Ma; Jiayan Qi; Zhiyu Zhang; Lirong Zhang; Mufeng Liang; Hongyuan Zeng; et al. (Journal of Environmental Management, 2025)

Does coal mining exert a greater influence than vegetation restoration on streamflow variation? Evidence from the Loess Plateau, China - Jinkai Luan; Ning Ma; Ran Zhang; Wei Li (Journal of Environmental Management, 2025)

Diversity and functional roles of viral communities in gene transfer and antibiotic resistance in aquaculture waters and microplastic biofilms - Yanwen Ma; Xiangli Dong; Yuman Sun; Bin Li; Haiping Ma; Hongfei Li; Xinyu Zhao; Suzhen Ran; Jintao Zhang; Yingying Ye; Jiji Li (Environmental Pollution, 2025)

Enhancing interfacial charge transfer efficiency via π-π interaction in PTA/VC-CN S-scheme heterojunction for efficient photocatalytic CO2 conversion - Sirui Liu; Qianjin Ye; Qin Li; Zhanzhen Ma; Ran Yang; Di Li; Deli Jiang (Chemical Engineering Journal, 2025)

Structural optimization and mechanical property analysis of butterfly valves based on Kriging surrogate model - Lei Shi; Tao Yang; JiangYan Ma; Lin Huang; Ao Tian; Yang Xuan; Yan Tian; Ran Gao (Building and Environment, 2025)

Data-driven differentiable model for dynamic prediction and control in wastewater treatment - Yun-Peng Song; Wen-Zhe Wang; Yu-Qi Wang; Wan-Xin Yin; Jia-Ji Chen; Hao-Ran Xu; Hao-Yi Cheng; Fang Ma; Han-Tao Wang; Ai-Jie Wang; Hong-Cheng Wang (Water Research, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Impact of microplastics exposure on the reconfiguration of viral community structure and disruption of ecological functions in the digestive gland of Mytilus coruscus - Xinjie Liang; Bin Li; Xiangli Dong; Xinyu Zhao; Hongfei Li; Yingying Ye; Haiping Ma; Suzhen Ran; Jiji Li (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Enhanced La0.875Ce0.125CoO3 catalyst for Hg0 removal from low-temperature flue gas: H2O and SO2 resistance performance and mechanism - Jie Gao; Zijun Ran; Jingyu Ran; Xin Huang; Chuan Ma; Yunlin Shao (Fuel, 2025)

Effects of nitrogen deposition on temporal stability and resistance of the alpine steppe plant communities on the Qinghai-Tibetan Plateau - Ran Zhang; Hao Shen; Shikui Dong; Qiang Yu; Bing Zhang; Jiannan Xiao; Shuai Li; Hui Zuo; Hang Shi; Fengcai He; Ke Zhang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Rotational grazing can enhance the soil available nutrients rather than plant diversity to promote ANPP of alpine steppe - Fengcai He; Shikui Dong; Juejie Yang; Xinghai Hao; Chunhui Ma; Hao Shen; Jiannan Xiao; Yu Li; Ran Zhang; Hang Shi; Ziying Wang; Yuhao Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Parameterization of surface roller evolution in wave-induced current modeling - Chao Ji; Qi Jiang; Dianguang Ma; Yuefeng Wu; Guoquan Ran; Xianwei Kong; Qinghe Zhang (Ocean Modelling, 2025)

Efficient inactivation of antibiotic resistant bacteria by iron-modified biochar and persulfate system: Potential for controlling antimicrobial resistance spread and mechanism insights - Ran Duan; Shuanglong Ma; Yanbing Ma; Shengjun Xu; Guangxin Li; Haichao Fu; Xujin Wu; Jinge Du; Peng Zhao (Journal of Hazardous Materials, 2025)

Osmotic and cold stress-induced viable but non-culturable state in Lacticaseibacillus paracasei Zhang: A transcriptome analysis - Qiuhua Bao; Baoyi Yuan; Xuebo Ma; Xin Zhao; Ran Gao; Jianan Li; Lai-Yu Kwok (International Dairy Journal, 2025)

Air flow field Testing, simulation and Optimization of CO2 air-source heat pump outdoor unit arrays - Li Xiaoyu; Shi Lin; Ma Li; Xu We; Wang Tiansheng; Zheng Siyu; Tian Ran; Yuan Jing; Cui Yujia (Energy and Buildings, 2025)

Synergistic enhancement of volatile fatty acid production from waste activated sludge by citric acid assisted potassium ferrate co-pretreatment: crucial role of citric acid - Ling Wang; Yurun Ma; Chenxin Zhu; Huan Liu; Ran Gao; Yue Ma; Xiaodong Wang; Xuejun Bi; Heliang Pang (Chemical Engineering Journal, 2025)

MCPA-Na exposure in aquatic systems: disruption of pathways and increased susceptibility to infection in fish - Yanxia Lin; Ran Shi; Mengzhen Wang; Yali Wang; Yunfan Han; Yongcui Ma; Liyin Li; Xiaohua Xia (Aquatic Toxicology, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Shrinking cities in China's urban network: a data-driven exploration of migration and investment flows - Yuzhou Chen; Ran Tao; Qiwei Ma; Mingshu Wang (Applied Geography, 2025)

Spatial Trajectory Tracking of Underactuated Autonomous Underwater Vehicles by Model–Data-Driven Learning Adaptive Robust Control - Linyuan Guo; Ran Zhou; Qingchang Guo; Liran Ma; Chuxiong Hu; Jianbin Luo (Journal of Marine Science and Engineering, 2025)
This paper aims to solve the spatial trajectory tracking control problem of underactuated autonomous underwater vehicles (AUVs) in the presence of system parameter uncertainties and complex external disturbances. To accomplish this goal, a model–data-driven learning adaptive robust control (LARC) strategy is introduced for AUVs. Firstly, a serial iterative learning control (ILC) approach is introduced as feedforward compensation, and then the corresponding trajectory tracking error dynamics model, the Feedforward Compensation–Line of Sight (FFC-LOS) guidance law, and the feedforward compensation-based kinematics controller are designed. Secondly, the dynamics controller is designed for AUVs, which consists of a linear feedback term, a nonlinear robust feedback term, an adjustable model compensation term, and a fast dynamic compensation term. In this control framework, the robust control and fast dynamic compensation parts are utilized to deal with nonlinear uncertainties and disturbances, the projection-type adaptive control part solves the influence caused by the uncertainty of system parameters, and the serial ILC part that is a data-driven learning method can further improve the trajectory tracking accuracy for repetitive tasks. Finally, comparative simulations under different scenarios and different types of disturbances are performed to verify the effectiveness of the proposed control strategy for AUVs.

A Fenton-integrated siphon evaporator for efficient removal of volatile fecal odors during interfacial steam generation - Zhaohe Cheng; Yuanlu Xu; Tiantian Chen; Ran Yu; Bowen Lv; Qiao Ma; Xinfei Fan (Journal of Environmental Chemical Engineering, 2025)

Modulating electron transfer in porous Cu-modified g-C3N4 for enhancing adsorption-photocatalytic synergistic removal of tetracycline hydrochloride - Ran Ma; Chunshan Li; Yumeng Su; Shengtai Hou; Wenwen Zhang; Hongjie Wang (Journal of Environmental Chemical Engineering, 2025)

An emulsion gel made by waxy maize starch hydrogel incorporated with tea polyphenols/exopolysaccharides: Structure and stability properties, antioxidant and delivery function - Cuicui Duan; Shunan Hu; Ran Wang; Cheng Wu; Yi Zhang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Schistosoma japonicum cystatin attenuated CLP-induced sepsis in mice though inducing tolerogenic dendritic cells and regulatory T cells - Yi-Xiang Wang; Yi-Dan Ma; Hui-Hui Li; Wen-Juan Duo; Qi-Wang Jin; Kai-Jun Zhou; Yan-Ran Gao; Jun-Nan He; Yu-Jie Xie; Liang Chu; Xiao-Di Yang (Comparative Immunology, Microbiology and Infectious Diseases, 2025)

Quantitative deciphering of mechanical response mechanism in lithium-ion batteries via DIC-assisted indentation - Zhanglong Yu; Xiaoli Ma; Zengming Wan; Ran Xu; Hang Zhang; Zhefeng Gao; Xueling Shen; Yanyan Fang; Fang Lian (Chemical Engineering Journal, 2025)

Regulation of sulfurization degree: A strategy to improve the electrochemical performance of MnCo2O4@MnCo2S4 composites in supercapacitors - Ding Shen; Ran Zhang; Yonghui Ma; Jianqiang Niu; Dong Xia; Youzhi Yang; Zhaoqi Ren; Yanzhao Song; Shuang Wei; Wei Dong (Chemical Engineering Journal, 2025)

Constructing a Li+-rich interlayer onto lithium anode for boosting the performance of high-voltage all-solid-state lithium metal batteries - Jinhai Liu; Kexin Liang; Linyuan Ma; Ran Bi; Yuanfu Deng (Chemical Engineering Journal, 2025)

Deciphering drought adaptation in Eucommia ulmoides: From the rhizosphere microbiota to root metabolites - Xueqian Zhang; Shuangshuang Hou; Xinyu Ma; Chenglong Li; Qingsong Ran; Yanfeng Han; Chunbo Dong (Applied Soil Ecology, 2025)

A High-Precision Method for Evaluating the Similarity of Maritime Vessel Trajectories - Ran Ji; Mengkai Ma; Jian Dong; Sen Wang (Journal of Marine Science and Engineering, 2025)
This study investigates the demand for high-precision trajectory similarity assessment in intelligent maritime navigation. This is done by analyzing discrepancies between GPS-derived trajectories and actual vessel paths, while identifying critical limitations in existing evaluation methods. To address these challenges, we propose a robust framework that integrates three core innovations: firstly, a linear feature accuracy-constrained resampling method to ensure computational precision under diverse complexity conditions, validated through experimental verification; secondly, a shape feature extraction and transformation protocol designed to maintain consistency across multi-scale and heterogeneous operational scenarios; thirdly, a quantitative similarity evaluation criterion based on extracted shape characteristics, enabling systematic alignment between localized trajectory segments and historical navigation patterns. The experimental results confirm the method’s enhanced robustness and its capability to bridge local and global trajectory comparisons, demonstrating that shape-driven quantification significantly refines similarity analysis. This approach advances intelligent maritime systems by providing a technically rigorous solution for real-time decision support and actionable insights into next-generation navigation applications.

Spatiotemporal evolution and influencing factors of ecosystem services on Hainan Island from 1985 to 2022: Insights from long-term annual assessments and spatial econometric models - Jie Zhang; Chong Jiang; Jianjun Qu; Jinxin Shi; Yuhe Ma; Di Liu; Ran Wang (Journal of Environmental Management, 2025)

Simultaneous extraction and in situ separation of flavonoids and alkaloids from mulberry leaves using a pH-responsive deep eutectic solvent/water system - Ruili Ma; Weiguo Wu; Yikang Shu; Ran Gao; Ziyu Wang; Daoquan Tang; Yan Du; Shuai Ji (Food Chemistry, 2025)

CRISPR-RPA biosensor with digital glucometer-based diagnostics of zoonotic fish-borne clonorchiasis - Xiaoxiao Ma; Jing Ding; Junpeng Song; Bin Tang; Yiming Fang; Ran Wang; Mingyuan Liu; Xiaolei Liu; Chen Li (Food Control, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Glutaraldehyde-crosslinked chitosan microspheres encapsulating La(OH)3 by electrospraying for efficient remediation of fluoride ions - Shaoju Jian; Jianyi Liu; Jinlong Wu; Weisen Yang; Li Ran; Jiapeng Hu; Gaigai Duan; Haoqi Yang; Jianxiu Ma; Shaohua Jiang (Chemical Engineering Journal, 2025)

Evolution of interfacial electro-chemo-mechanics in high-energy-density NCM811||Si/C-composite Lithium-ion pouch cells - He Ma; Shujun Cai; Ran Song; Kexuan Jing; Min Wu; Weizong Wang; Yurong Ren; Qian Zhao; Zhengping Ding (Chemical Engineering Journal, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Construction of a NIR fluorescent probe for tracking mitochondrial HOCl during liver injury - Cailing Fan; Kaifu Ma; Ran Chen; Tianyu Zhang; Yonghao Song; Lei Liu; Weijie Chi; Qinxi Dong; Wei Shu; Chaoyuan Zeng (Journal of Photochemistry and Photobiology B: Biology, 2025)

Manganese on P, N self-doped biochar toward promoting periodate activation for highly efficient tetracycline degradation: Performance and mechanisms - Xiaofang Pan; Hong Ma; Rongning Zhang; Ran Deng; Meng Li; Binfei Yang; Ruiying Zhu; Li Zhao; Yong Liu; Xiaobo Gong (Journal of Environmental Chemical Engineering, 2025)

Mesomechanical weakening mechanism of coal modified by nanofluids with disparately sized SiO2 nanoparticles - Quanle Zou; Tengfei Ma; Jinyan Liang; Bochao Xu; Qican Ran (International Journal of Rock Mechanics and Mining Sciences, 2025)

Simultaneous extraction of flavonoids and saponins from functional food via basic deep eutectic solvent-assisted mechanochemical extraction - Yi-Wen Wu; Jie Zhang; Xin-Ran Ma; Jun Cao (Food Chemistry, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Glaesserella parasuis induces tissue transglutaminase-mediated fibrinogen crosslinking through NF-κB activation - Bin Ma; Yanxi Wan; Ran Zhuo; Huimin Gong; Yuan Gao; Rui Luo; Xueying Hu; Kexin Hua; Yuncai Xiao; Hui Jin (Veterinary Microbiology, 2025)

Multi-objective optimization design of an umbilical cross-sectional layout based on the sequential least squares quadratic programming algorithm - Qian Ran; Meng Li; Fusen Peng; Yanlian Du; Yijun Shen; Yongqi Ma (Ocean Engineering, 2025)

Mooring optimization for net-cage group system based on NSGA-III multi-objective genetic algorithm - Sulian Zhou; Shaowen Gu; Hongwei Wang; Gang Ma; Qingao Ran; Jin Wen (Ocean Engineering, 2025)

Magnesium modified algae biochar for phosphorus adsorption: Synthesis, experimental analysis, DFT calculations and regeneration - Zhiying Guo; Degang Zhang; Liping Ma; Quxiu Dai; Ren Yang; Ran Ao (Journal of Water Process Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Resveratrol Alleviates Arsenic Exposure-Induced Liver Fibrosis in Rats by Inhibiting Hepatocyte Senescence - Qiming Ran; Dingyi Song; Qi Wang; Dapeng Wang; Xiong Chen; Aihua Zhang; Lu Ma (Biological Trace Element Research, 2025)

Buoy-based monitoring of sea surface carbon dioxide partial pressure at Qingdao coastal area - Lu Cao; Su Li; Shuwei Zhang; Ning Wu; Keke Zhang; Wenqing Li; Ran Ma; Dongzhi Chu; Ni Wang; Yan Liu (Frontiers in Marine Science, 2025)
Continuous time series observations of seawater carbon dioxide partial pressure ( p CO 2 ) are crucial for documenting temporal variations in air-sea CO 2 fluxes. To examine the seawater p CO 2 variation and its influence factors at Qingdao coastal waters, a high-resolution observation of seawater p CO 2 near the Xiaomaidao Island was conducted from May 29 to July 25 in 2024. Sea surface p CO 2 varied from 519 µatm to 717 µatm during this monitoring period, with an obvious decline and rise from July 12 to 21. The variation of seawater p CO 2 was mainly affected by the increasing sea surface temperature, except for the period of p CO 2 decrease which was caused by Ulva prolifera bloom. Accompanied by the increase of U. prolifera , sea surface p CO 2 decreased to 563 µatm, then the coverage of U. prolifera decreased and sea surface p CO 2 rose to 669 µatm during period of July 12 to 21. The observation site acted as a source for atmospheric CO 2 throughout the monitoring period, with air-sea CO 2 flux ranging from less than 1 mmol m -2 d -1 to over 100 mmol m -2 d -1 , resulting in a total CO 2 release of 334 mmol m -2 . Thus, it is essential for high-resolution measurement of p CO 2 in coastal areas.

Chronic environmental exposure to polystyrene microplastics increases the risk of nonalcoholic fatty liver disease - Yujie Shi; Runyang Hong; Zhencheng Fan; Ran Huan; Yajie Gao; Min Ma; Tingting Liu; Chun Pan (Toxicology, 2025)

Experimental validation and mechanistic elucidation of crack division and two-phase flow-mediated sealing in coalbed methane extraction boreholes - Dezhi Ran; Jianwei Cheng; Yejiao Liu; Qiang Fu; Zhiyuan Ma; Jing Mei (International Journal of Rock Mechanics and Mining Sciences, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Anaerobic co-digestion of winery wastewater with sewage sludge for methane production: Complementary feedstocks and potential direct interspecies electron transfer - Zhixuan Ma; Lifang Yu; Ze Wang; Xin Tian; Lanxiang Zheng; Ran Liu (Fuel, 2025)

Simultaneous enantioseparation of citrus flavonoids in chiral microemulsion electrokinetic chromatography using deep eutectic solvents - Huang-Fei Jin; Qian-Xue Shen; Xin-Ran Ma; Jun Cao (Food Chemistry, 2025)

Synergistic improvement of RuO2/CeO2 catalysts on Hg0 oxidation from SO2-containing flue gas: A theoretical and experimental study - Zhi He; Wei He; Jingyu Ran; Chuan Ma; Xin Huang; Yunlin Shao (Chemical Engineering Journal, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Identification and hazard prioritization of hydrophobic organic chemicals in flowback and produced water particles: Implications for water management - Huiju Lin; Cheng Zhong; Ran Wen; Tsz Hin Ma; Ding He; Jonathan W. Martin; Greg G. Goss; Daniel S. Alessi; Yuhe He (Water Research, 2025)

Enhanced priming effect in agricultural soils driven by high-quality exogenous organic carbon additions: A meta-analysis - Yuyao Zhang; Hongyu Hu; Yiguo Ran; Ping Huang; Yunlong Cai; Lin Chen; Congzhi Zhang; Xin Gao; Donghao Ma; Jiabao Zhang (Science of The Total Environment, 2025)

Optimization design of floating offshore wind turbine mooring system based on DNN and NSGA-III - Hongwei Wang; Qingao Ran; Gang Ma; Jin Wen; Jianhua Zhang; Sulian Zhou (Ocean Engineering, 2025)

Suspended sediment (SPS) triggers nitrogen retention by altering microbial network stability and electron transport behavior during the aerobic-anoxic transition - Xiaoyan Liu; Tingting Pei; Guojia Xu; Tinglin Huang; Yaoguo Wu; Xiaowei Jin; Yi Cao; Ran Sun; Sihai Hu; Pathmalal M. Manage; Xiang Liu; Tao Liu; et al. (Journal of Environmental Management, 2025)

Characterization of ornithine decarboxylase with histidine decarboxylase activity in natural histidine decarboxylase gene deletion Enterobacter hormaechei RH3 - Huijie Pei; Yilun Wang; Wei He; Yue Zhang; Lamei Yang; Jinhai Li; Yixuan Ma; Xinjie Hu; Shuhong Li; Jianlong Li; Kaidi Hu; Aiping Liu; et al. (Food Microbiology, 2025)

Improving charge separation in poly(heptazine imide) via synergy of covalent S-scheme heterojunction and Schottky junction for efficient photocatalytic CO2 reduction - Ran Yang; Qin Li; Zhanzhen Ma; Sirui Liu; Dan Tian; Di Li; Deli Jiang (Chemical Engineering Journal, 2025)

Self-assembled supramolecular pillared arrays as bionic interface to stabilize zinc metal anodes - Kang Ma; Shuang Chen; Ran Zeng; Zhen Luo; Yancheng Wang; Yinzhu Jiang; Hongge Pan; Deqing Mei; Kai Tao (Chemical Engineering Journal, 2025)

A green and effective glucoside surfactant assisted micellar electrokinetic chromatography for the separation of phenolic compounds from medicinal plant using response surface methodology - Qian-Xue Shen; Yan-Hua Jiao; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Transfer of pesticides and metabolites in corn: Production, processing, and livestock dietary burden - Fengjiao Hao; Xiaoqing Wang; Feixiang Ma; Ran Wang; Fengshou Dong; Xinglu Pan; Xiaohu Wu; Yongquan Zheng; Jun Xu (Science of The Total Environment, 2024)

Targeting modulation of intestinal flora through oral route by an antimicrobial nucleic acid-loaded exosome-like nanovesicles to improve Parkinson’s disease - Weitong Cui; Zhiyong Guo; Xingyu Chen; Ran Yan; Wenjuan Ma; Xiao Yang; Yunfeng Lin (Science Bulletin, 2024)

Covalent triazine frameworks as particle electrode for three-dimensional photoelectrocatalytic degradation of oxytetracycline: Synergy effects, pathway, and mechanism - Wenwen Zhang; Guangyang Wang; Heng Yang; Ran Ma; Hongjie Wang (Journal of Environmental Management, 2024)

Explores the environmental hazards associated with plastic food packaging and discusses degradation processes - Jie Xu; Zhuoqing Ran; Yongfang Jiang; Yongping Leng; Xue-Qing Zhan; Changchang Zhu; Changbo Zhang; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2024)

Tolerance of Cu-SSZ-13 catalysts to potassium sulfate: Strong Brønsted acid sites and copper species - Liping Liu; Yang Gao; Yue Ma; Xiaodong Wu; Letong Yang; Xiangju Meng; Rui Ran; Duan Weng (Journal of Environmental Chemical Engineering, 2024)

Satellite detection of sea fog and low clouds in the Arctic in the daytime during the summer through multiple sources of infrared remote sensing - Huiyun Ma; Zengwei Liu; Yinze Ran; Xiaojing Wu; Huihui Feng (Global and Planetary Change, 2024)

Screening, Gene Cloning and Expression of Cellulase-Producing Strain Bacillus subtilis Xh-16 - Xiaoxi Zeng; Xinping Ren; Ruotong Wu; Yuanke Zhang; Cheng Zhang; Song Ran; Liang Ma (Current Microbiology, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Analyzing performance and microbial mechanisms in an incineration leachate treatment after waste separation: Integrated metagenomic and metaproteomic analyses - Han Wang; Xiaoqian Ma; Xiaochuan Ran; Tong Wang; Mingda Zhou; Chao Liu; Xiang Li; Min Wu; Yayi Wang (Science of The Total Environment, 2024)

Voluntary walking related joint movement training with targeted epidural electrical stimulation enabled neural recovery for individuals with spinal cord injury - Xi Zhang; Yang Lu; Boyang Zhang; Hongda Li; Qingyu Yao; Junhong Lim; Yunyue Wei; Kaibo He; Chenhui Zuo; Yanan Sui; Bozhi Ma; Mingshan Ran; et al. (Science Bulletin, 2024)

Resistance monitoring of diamide insecticides and characterization of field-evolved chlorantraniliprole resistance among Chinese populations of the tomato pinworm Phthorimaea (=Tuta) absoluta (Lepidoptera: Gelechiidae) - Xiaoli Ma; Cheng Qu; Jiaqi Yao; Jixing Xia; Chen Luo; Raul Narciso C. Guedes; Ran Wang (Pesticide Biochemistry and Physiology, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

LiF-enriched interphase promotes Li+ desolvation and transportation enabling high-performance carbon anode under wide-range temperature - Wenbin Luo; Kuo Li; Tu Ran; Di Ma; Xingkun Chen; Haisong Wang; Yi Cheng; Xiaofei Yang (Chemical Engineering Journal, 2024)

Endgroup engineering of the third component for high-efficiency ternary organic solar cells - Chanyin Cao; Xueqing Ma; Xinming Zheng; Guangliu Ran; Ziqing Bian; Yahui Liu; Wenkai Zhang; Zhishan Bo (Chemical Engineering Journal, 2024)

Mitigating interfacial recombination enabling efficient semitransparent organic photovoltaics - Hailin Yu; Jiayu Wang; Yuanhao Li; Tianyu Liu; Yufei Gong; Cenqi Yan; Qichao Ran; Qun Luo; Zupan Mao; Xin Wei; Lei Meng; Changqi Ma; et al. (Chemical Engineering Journal, 2024)

Polyamide and deep eutectic solvent assisted matrix solid-phase dispersion microextraction for strong hydrophobic compounds - Yi-Wen Wu; Xin-Ran Ma; Xin Peng; Xudong Cai; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Contribution to energy conservation and quality improvement of frozen pork via contact/contactless immersion freezing in NaCl solution - Yu Zhou; Xia Yu; Ran Xiao; Li-fang Zou; Qing-fei Du; Fei Ma; Cong-gui Chen (Meat Science, 2024)

Precise fine-tuning of the defect degree in FeNi-TDC nanoarrays via fluorinated acetic acid for rapid urea-assisted hydrogen production in seawater - Qianqian Wang; Xiaoyan Ma; Fengjin Qu; Ran bi; Senyang Song; Pengcheng Ma; Jing Sun; Fang Chen; Qiufan Tang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Effects of arsenic exposure on blood trace element levels in rats and sex differences - Xiaoqian Ran; Xi Yan; Hongbin Zhuang; Zhiyuan Liang; Guanwei Ma; Xiaolu Chen; Yuhan Huang; Xukun Liu; Peng Luo; Ting Hu; Jun Zhang; Liming Shen (BioMetals, 2024)

OsHRZ1 negatively regulates rice resistant to Magnaporthe oryzae infection by targeting OsVOZ2 - Jia-ying Sun; Zeng-ran Zhou; Yu-qi Wang; Dong-yu Zhu; Dian-rong Ma (Transgenic Research, 2024)

A data-knowledge joint-driven reinforcement learning algorithm based on guided policy and state-prediction for satellite continuous-thrust tracking - Xiao Wang; Jiake Li; Lu Cao; Dechao Ran; Mingjiang Ji; Kewu Sun; Yuying Han; Zhe Ma (Advances in Space Research, 2024)

Morphological characterization and transcriptome analysis of opercular deformity in golden pompano (Trachinotus ovatus) - Yuwei Wu; Dihao Huang; Qian Ma; Liuyong Wang; Qiling Zhou; Chunli Ran; Gang Chen (Aquaculture, 2024)

The joint production of green diesel and activated carbon from spent coconut shells (SCS): An energy techno-economic and Life Cycle Assessment case for China - Buqing Ran; Yuxiang Ma; Hong Tian; Ye Zhu; Chenchen Qi; Linli Shang (Journal of Cleaner Production, 2024)

Effect of supercritical carbon dioxide on protein structure modification and antimicrobial peptides production of Mongolian cheese and its in vitro digestion - Yawen Geng; Yuanrong Zheng; Ran Zhou; Ming Ma (Food Research International, 2024)

Successive application of controlled-loss urea improves grain yield and economic benefit in maize-wheat cropping systems - Lisha Shangguan; Zejie Ye; Dengke Hou; Wenlu Zhai; Zhongzhou Feng; Ran Zhang; Yingxin Xie; Geng Ma; Chenyang Wang; Dongyun Ma; Tiancai Guo; Xu Zhao (European Journal of Agronomy, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

GEO satellite on-orbit refueling and debris removal hybrid mission planning under uncertainty - Weikui Liang; Hui Zhi; Peng Han; Guangtao Ran; Guangfu Ma; Yanning Guo (Advances in Space Research, 2024)

Assessing the impact of passenger compliance behavior in CAVs on environmental benefits - Zheng Xu; Zhe Zheng; Dong Xiao; Ran Tu; Wanjing Ma; Nan Zheng (Transportation Research Part D: Transport and Environment, 2024)

Fe/Co bimetallic nanozyme disrupting tumorous Self-Regulatory pathways to potentiate ferroptosis - Qing Liu; Qian Chen; Xi Deng; Yutong Zhu; Zhangpeng Shi; Runjie Miao; Ming Ma; Nian Ran; Cheng Li; Hangrong Chen (Chemical Engineering Journal, 2024)

Improvement of Coagulation and Membrane Filtration Performance in Hybrid Coagulation-UF-RO System for Chemical Mechanical Polishing Wastewater Treatment: Effect of Coagulants - Jianglei Xiong; Ran Ma; Yuming Tian; Liangsheng Yang; Yuxuan He; Jin Qian; Weijie Wu; Yaguang Gao; Jiahao Luo; Donglei Xu; Jigang Shen (Water, Air, & Soil Pollution, 2024)

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

In situ acid production by organic matter induced with trace homogeneous Fenton reagent for membrane fouling control - Rui Miao; Haoxue Ran; Yifan Yang; Yanfei Li; Zhuowen Ma; Yongtao Lv; Xiaorong Meng; Miaolu He; Lei Wang (Water Research, 2024)

Exploring secondary aerosol formation associated with elemental carbon in the lower free troposphere - Li Li; Qiyuan Wang; Jie Tian; Yaqing Zhou; Nan Ma; Huikun Liu; Yang Zhang; Shuoyuan Chen; Jin Wang; Yukun Chen; Weikang Ran; Jianjun Li; et al. (Science of The Total Environment, 2024)

Engineering of molecularly imprinted cavity within 3D covalent organic frameworks: An innovation for enhanced extraction and removal of microcystins - Yu-Hong Tang; Tian-Tian Ma; Xu-Qin Ran; Yukun Yang; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

Meta-analysis addressing the potential of antibiotic resistance gene elimination through aerobic composting - Hongge Wang; Xuan Wang; Lu Zhang; Xinyuan Zhang; Yubo Cao; Ran Xiao; Zhaohai Bai; Lin Ma (Waste Management, 2024)

Synergistic use of photocatalysis and convergent paired electrolysis for nickel-catalyzed arylation of cyclic alcohols - Zhao-Ran Liu; Xiao-Yu Zhu; Jian-Feng Guo; Cong Ma; Zhiwei Zuo; Tian-Sheng Mei (Science Bulletin, 2024)

Genome-wide association study and genomic selection of spike-related traits in bread wheat - Huiyuan Xu; Zixu Wang; Faxiang Wang; Xinrong Hu; Chengxue Ma; Huijiao Jiang; Chang Xie; Yuhang Gao; Guangshuo Ding; Chunhua Zhao; Ran Qin; Dezhou Cui; et al. (Theoretical and Applied Genetics, 2024)

Enhanced interfacial effect via acid theory with boosted photocatalytic performance of nitenpyram removal - Ran Chen; Bo Xu; Heping Cheng; Qianqian Fang; Minghai Ma; Liping Qian; Shunli Wan; Shengyou Xu; Yan Li; Lei Zhang; Shikai Xiang (Chemosphere, 2024)

Study on the mechanism of arsenic-induced renal injury based on SWATH proteomics technology - Xiaolu Chen; Xi Yan; Xiaoxiao Tang; Yi Wang; Xinglai Zhang; Xueshan Cao; Xiaoqian Ran; Guanwei Ma; Ting Hu; Ayesha Qureshi; Peng Luo; Liming Shen (Journal of Trace Elements in Medicine and Biology, 2024)

Dynamic risk evaluation of supersaturated dissolved gas at a confluence with unsteady flow conditions - Zhuo Chen; Jingjie Feng; Ran Li; Qian Ma; Ruifeng Liang; Jingying Lu; Jingyang Xue (Journal of Hydrology, 2024)

Zonation of bulk and rhizosphere soil bacterial communities and their covariation patterns along the elevation gradient in riparian zones of three Gorges reservoir, China - Weitao Jia; Ping Huang; Kai Zhu; Xin Gao; Qiao Chen; Jilong Chen; Yiguo Ran; Shanshan Chen; Maohua Ma; Shengjun Wu (Environmental Research, 2024)

Facile synthesis of Ce(III)-rich cerium oxyhydroxide and its unselective adsorption of Sb(III) and Sb(V) via oxygen vacancies - Yaopeng Zhang; Ran Zhang; Miaojia Du; Hui Chen; Chensi Shen; Qinqi Zhu; Haijiao Xie; Chenye Xu; Chunyan Ma; Fang Li (Chemical Engineering Journal, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Border effects for domestic travel in China during COVID-19 pandemic - Qiwei Ma; Anqi Liu; Yuzhou Chen; Ran Tao (Journal of Transport Geography, 2024)

High contributions of fossil fuel sources to char-EC/soot-EC at a high-altitude site: Direct radiative effects and transport pathway - Huikun Liu; Qiyuan Wang; Yao Qu; Jie Tian; Li Li; Nan Ma; Yaqing Zhou; WeiKang Ran; Hui Su; Yongming Han; Giulia Pavese; Junji Cao (Fuel, 2024)

Construction of dual functional CuAl-LDHs nanocomposite loaded with IGF2BP3 siRNA for enhanced therapy of gastric cancer - Haiping Li; Yuying Zhang; Bo Huang; Feifei Yang; Qiang Ma; Xiaolin Wang; Yuying Liu; Junwu Ren; Xiaojuan Pan; Ce Liang; Shimin Wang; Hao Ning; et al. (Chemical Engineering Journal, 2024)

Hierarchically porous magnetic biochar as an amendment for wheat (Triticum aestivum L.) cultivation in alkaline Cd-contaminated soils: Impacts on plant growth, soil properties and microbiota - Haichao Fu; Shuanglong Ma; Long Wang; Weijie Xue; Shiwu Xiong; Fuqing Sui; Hongen Liu; Chang Li; Guangxin Li; Ran Duan; Peng Zhao (Chemosphere, 2024)

The impact of regional policy implementation on the decoupling of carbon emissions and economic development - Xiaoyue Ma; Congyu Zhao; Chenchen Song; Danni Meng; Mei Xu; Ran Liu; Yamin Yan; Zhengguang Liu (Journal of Environmental Management, 2024)

Erosional modulation of the balance between alkalinity and acid generation from rock weathering - Sen Xu; Aaron Bufe; Si-Liang Li; Erica D. Erlanger; Lishan Ran; Jun Zhong; Ci-Jian Yang; Liwei Zhang; Tingting Ma; Dirk Sachse (Geochimica et Cosmochimica Acta, 2024)

Transformation and migration mechanism of carbon and sulfur in lignite’s chemical looping gasification using carbide slag - Jie Yang; Lan shao; Liping Ma; Senlin Dong; Wang Du; Quxiu Dai; Longgui Xie; Ran Ao; Zhiying Guo (Fuel, 2024)

Effect of SiO2-H2O nanofluids on wettability of pulverized coal and the modification mechanism - Jiajia Zhao; Shixiang Tian; Quanle Zou; Honggao Xie; Qican Ran; Tengfei Ma; Xuan Zhang (Fuel, 2024)

Identification, characterization and functional analysis of Rap1 in response to bacterial infection in tilapia - Jingjing Ran; Hui Du; Jia Liu; Chuizheng Kong; Haixiang Ma; Tianqiang Liu; Tao Liu; Gaoxue Wang; Erlong Wang (Aquaculture, 2024)

Exploration of risk analysis and elimination methods for a Cr(VI)-removal recombinant strain through a biosafety assessment in mice - Wanting You; Qiuying An; Dongbei Guo; Zebo Huang; Lulu Guo; Zigui Chen; Hao Xu; Guangshun Wang; Yeting Weng; Zhangye Ma; Xiaoxuan Chen; Feng Hong; et al. (Science of The Total Environment, 2024)

Effect of acetochlor on the symbiotic relationship between microalgae and bacteria - Zikang Wang; Simin Yu; Yufan Nie; Ran Liu; Wentao Zhu; Zhiqiang Zhou; Yongqiang Ma; Jinling Diao (Journal of Hazardous Materials, 2024)

Fe-MOFs/CuS nanocomposite-mediated peroxymonosulfate activation for tetracycline degradation: Boosted dual redox cycles - Rui Ma; Zhijie Chen; Weihang Xu; Ran Yu; Yichu Zhang; Fan Chen; Xiaoming Peng; Bing-Jie Ni; Jin Qian (Journal of Cleaner Production, 2024)

Understanding the effects of A-site Ag-doping on LaCoO3 perovskite for NO oxidation: Structural and magnetic properties - Ran Ao; Tao Pu; Liping Ma; Quxiu Dai; Jie Yang; Wengang Li; Longgui Xie; Zhiying Guo (Journal of Environmental Management, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Development of polymorphic simple sequence repeat markers in Agastache rugosa and their application in genetic evaluation and cross-taxon transferability of Agastache species - Hye Ran Shin; Ick Hyun Jo; Raveendar Sebastin; Jinsu Gil; Gi Yeong Kim; Suyun Moon; Hyun-Seung Park; Sewon Oh; Jong Won Han; Kyung Ho Ma; Yi Lee; Daeil Kim; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Effect of indigenous Saccharomyces cerevisiae strains on microbial community successions and volatile compounds changes during Longyan wine fermentation - Xiaodi Wang; Chao Dang; Yaqiong Liu; Xiaoxin Ge; Ran Suo; Qianyun Ma; Jie Wang (Food Bioscience, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

High-valence metal engineered trimetallic organic framework derived S, C co-doped FeNiCeP nanospheres for proficient self-powered overall water splitting - Qianqian Wang; Xiaoyan Ma; Wei You; Pengcheng Ma; Ran Bi; Senyang Song; Fang Chen; Fengjin Qu; Xinli Wang; Pengfei Liu (Chemical Engineering Journal, 2024)

Effective free-standing electrodes with refined structure via sputtering Ti sublayer and altering working pressure for electrocatalytic benzaldehyde hydrogenation - Guanhua Cheng; Jiameng Sun; Yunfei Ran; Fuquan Tan; Wensheng Ma; Zhonghua Zhang (Chemical Engineering Journal, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Inherited zircons in Early Cretaceous dyke: Implication of growth and reworking of continental crust in the Jiaodong Peninsula - Yao Ma; Xuefei Liu; Yayun Liang; Shengchao Xue; Xiaoyu Ran (Tectonophysics, 2024)

Combined toxic effects of nanoplastics and norfloxacin on antioxidant and immune genes in mussels - Yichi Ma; Yiming Gao; Ran Xu; Daoji Li; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

Highly sensitive determination of multiple pesticide residues in foods by supercritical fluid chromatography coupled with ion mobility quadrupole time-of-flight mass spectrometry - Ying Shi; Huang-Fei Jin; Xin-Ran Ma; Jun Cao (Food Research International, 2024)

Pressure-induced gelation of blended milk and pea protein suspensions - Xingfa Ma; Ran Feng; Lilia Ahrné; Vibeke Orlien (Food Hydrocolloids, 2024)

Revealing varying relationships between wastewater mercury emissions and economic growth in Chinese cities - Yuanchun Zhou; Shu Ma; Wenhui Zhu; Qingquan Shi; Hongqiang Jiang; Ran Lu; Wenjun Wu (Environmental Pollution, 2024)

Effective electrosorption and recovery of phosphorus by capacitive deionization with a covalent organic framework-membrane coating electrode - Chengyi Wang; Ran Li; Yubo Xu; Zhongbao Ma; Yangbo Qiu; Chao Wang; Long-Fei Ren; Jiahui Shao (Desalination, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Fine-grained deep-water turbidite gas reservoirs in upper Bengal Fan - Yintao Lu; Buqing Shi; Xiwu Luan; Guozhang Fan; Weimin Ran; Xiaoyong Xu; Hongxia Ma; Dali Shao; Liangbo Ding; Haiqiang Wang (Marine and Petroleum Geology, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Improving the photodegradation efficiency of POPs in oily sewage: Design and synthesis of G-C3N4-based photocatalysts incorporating a pickering emulsion catalytic strategy - Biyun Su; Xueqiong Ma; Liangtao Ran; Shaowei Wu; Boli Hou (Journal of Environmental Chemical Engineering, 2023)

Regioselective [3 + 2] cycloaddition of diazo reagents and internal alkynes: Accessing regiosomers of highly substituted trifluoromethylpyrazoles - Shuo-Han Li; Ran Guo; Ning Lv; Yu Liu; Xiaodong Tang; Jun-An Ma (Journal of Fluorine Chemistry, 2023)

Lymph node-inspired immunoregulatory hydrogel with siRNA delivery property for postoperative glioblastoma treatment - Zide Wang; Huimin Geng; Yuqi Zhang; Yingzhao Shao; Dongchen Li; Zhiwei Li; Yuan Ma; Yulin Zhang; Kaiyan Xi; Zhiwei Xue; Guangpan Sun; Hanlin Zhong; et al. (Chemical Engineering Journal, 2023)

Core community drives phyllosphere bacterial diversity and function in multiple ecosystems - Ran Xue; Shan Liu; Erinne Stirling; Yiling Wang; Kankan Zhao; Haruna Matsumoto; Mengcen Wang; Jianming Xu; Bin Ma (Science of The Total Environment, 2023)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Mapping cropland suitability in China using optimized MaxEnt model - Xiaoliang Li; Kening Wu; Shiheng Hao; Zhang Yue; Zhao Ran; Jinliang Ma (Field Crops Research, 2023)

Phenotype-genotype mapping reveals the betaine-triggered L-arginine overproduction mechanism in Escherichia coli - Shuai Jiang; Heyun Wu; Zhuoyue Yao; Ran Li; Qian Ma; Xixian Xie (Bioresource Technology, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Mapping of suitable habitats for earthworms in China - Xiaoliang Li; Kening Wu; Shiheng Hao; Long Kang; Jinliang Ma; Ran Zhao; Yue Zhang (Soil Biology and Biochemistry, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

Advances in the application of metallic isotopes to the identification of contaminant sources in environmental geochemistry - Peng Wang; Jian Hu; Tingyi Liu; Jinke Liu; Shunrong Ma; Wenmin Ma; Jun Li; Houyi Zheng; Ran Lu (Journal of Hazardous Materials, 2023)

Potential effects of Ag ion on the host by changing the structure of its gut microbiota - Xin-Lei Wang; Nanyang Yu; Ying-Xue Ma; Hao-Ran Zhou; Chuan Wang; Si Wei; Ai-Jun Miao (Journal of Hazardous Materials, 2023)

Behavior of heavy metals in municipal sludge during dewatering: The role of conditioners and extracellular polymeric substances - Zhiying Guo; Liping Ma; Quxiu Dai; Yanhong Liu; Degang Zhang; Ran Ao (Journal of Environmental Management, 2023)

Improved hydrothermal stability of Cu-SSZ-13 by SAPO-34 modification: Framework stability and inter-particle migration - Yang Gao; Yue Ma; Xiaodong Wu; Rui Ran; Zhichun Si; Duan Weng (Fuel, 2023)

Carbon sequestration in paddy soils: Contribution and mechanisms of mineral-associated SOC formation - Cuiyun Niu; Liping Weng; Wanli Lian; Ran Zhang; Jie Ma; Yali Chen (Chemosphere, 2023)

pH-Regulated lignin as a green catalyst for Highly-Efficient CO2 cycloaddition - Yidan Ouyang; Bin Lei; Zhouqing Tan; Fen Hu; Zhao Wu; Jiaxue Wang; Yixuan Ma; Ran Zhang; Li Guo; Feifei Chen (Fuel, 2023)

Soil aggregates, carbon and nitrogen distribution, and water infiltration as influenced by mulching practices in a laterite mango (Mangifera indica L.) orchard - Chengming Yan; Dongsheng An; Baoshan Zhao; Haiyang Ma; Yanan Liu; Ran Kong; Junbo Su (Journal of Soils and Sediments, 2023)

Theory, Technology and Practice of Unconventional Petroleum Geology - Caineng Zou; Zhi Yang; Guosheng Zhang; Rukai Zhu; Shizhen Tao; Xuanjun Yuan; Lianhua Hou; Dazhong Dong; Qiulin Guo; Yan Song; Qiquan Ran; Zhen Qiu; et al. (Journal of Earth Science, 2023)

Periodic flooding enhances the function of soil Fe/Al oxides in stabilizing particulate organic carbon in a water level drawdown zone - Yiguo Ran; Kai Zhu; Maohua Ma; Shengjun Wu; Ping Huang (Soil and Tillage Research, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Nitrogen fertilizer alleviates rice yield loss without increasing global warming potential under elevated temperatures - Yingying Shen; Kailu Wang; Yufei Zhao; Liqing Yang; Wenzhe Liu; Tongyang Yin; Xueqin Wang; Xuan Ran; Hao Guo; Yuru Ma; Xinying Wu; Yao Chen; et al. (Field Crops Research, 2023)

Experimental and numerical study of laser-welded stainless steel slender I-section beam-columns - Hongdong Ran; Zhanpeng Chen; Yunmei Ma; Eugene OBrien; Yao Sun (Engineering Structures, 2023)

The pH dependence of photochemical reactions between methoxyphenols with Fe(III)-oxalates - Wangjin Yang; Jiawei Ma; Xiangli Nan; Ran Yan; Ning Tang; Tao Du; Chong Han (Atmospheric Environment, 2023)

QTL Detection for Internode Component Index in Wheat Using a RIL Mapping Population - Ran Qin; Tianhang Ma; Mingsu Cao; Xijian Liu; Xiaohan Zhou; Guimei Hu; Wen Zhong; Xiaohui Sun; Jingguo Xiao; Jiajin Dong; Wenchao Kong; Chunhua Zhao; et al. (Plant Molecular Biology Reporter, 2023)

Characteristics of Mining-Induced Fractures Under Inclined Coal Seam Group Multiple Mining and Implications for Gas Migration - Qican Ran; Yunpei Liang; Quanle Zou; Bichuan Zhang; Rifu Li; Zihan Chen; Tengfei Ma; Fanjie Kong; Han Liu (Natural Resources Research, 2023)

Consistent differences in brain structure and functional connectivity in high-altitude native Tibetans and immigrants - Xinjuan Zhang; Weiwei Xie; Wenrui Du; Yanqiu Liu; Jianzhong Lin; Wu Yin; Lihui Yang; Fengjuan Yuan; Ran Zhang; Haipeng Liu; Hailin Ma; Jiaxing Zhang (Brain Imaging and Behavior, 2023)

Characteristics for the sources and sinks of gravity waves in an orographic heavy snowfall event - Shuping Ma; Lingkun Ran; Jie Cao; Baofeng Jiao; Kuo Zhou (Frontiers of Earth Science, 2023)

Multifunctional injectable hydrogel promotes functional recovery after stroke by modulating microglial polarization, angiogenesis and neuroplasticity - Xiaoyu Ma; Fuhai Gao; Wei Su; Yuanyuan Ran; Tuerhong Bilalijiang; Yerasel Tuolhen; Guiqin Tian; Lin Ye; Zengguo Feng; Jianing Xi; Zongjian Liu (Chemical Engineering Journal, 2023)

Responses of Rice and Related Cadmium Transporter Genes to the Passivating Microbial Agent MBLHAP - Xiaoxi Zeng; Song Ran; Xiaoran Shen; Cheng Zhang; Hong Xu; Yilin Qi; Xinping Ren; Liang Ma (Current Microbiology, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Effects of light on growth, feeding rate, digestion, and antioxidation in juvenile razor clams Sinonovacula constricta - Mengqi Zhang; Fei Kong; Bin Ma; Deshui Chen; Zhaoshou Ran; Shuonan Ma; Kai Liao; Jiayi Cao; Lin Zhang; Xiaojun Yan; Jilin Xu (Aquaculture, 2023)

Photo-sterilization of groundwater by tellurium and enhancement by micro/nano bubbles - Dingren Ma; Ran Yin; Zhuocheng Liang; Qiwen Liang; Guizhi Xu; Qiyu Lian; Po Keung Wong; Chun He; Dehua Xia; Hui Lu (Water Research, 2023)

Optical Coherence Tomography in Cerebrovascular Disease: Open up New Horizons - Ran Xu; Qing Zhao; Tao Wang; Yutong Yang; Jichang Luo; Xiao Zhang; Yao Feng; Yan Ma; Adam A. Dmytriw; Ge Yang; Shengpan Chen; Bin Yang; et al. (Translational Stroke Research, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

Recognition of microplastics suspended in seawater via refractive index by Mueller matrix polarimetry - Jiajin Li; Hongyuan Liu; Ran Liao; Hongjian Wang; Yan Chen; Jing Xiang; Xiangrong Xu; Hui Ma (Marine Pollution Bulletin, 2023)

Xenogenetic evolutionary of integrons promotes the environmental pollution of antibiotic resistance genes — Challenges, progress and prospects - Ran An; Yuting Qi; Xu-Xiang Zhang; Liping Ma (Water Research, 2023)

Auxin alleviates cadmium toxicity by increasing vacuolar compartmentalization and decreasing long-distance translocation of cadmium in Poa pratensis - Ting Cui; Yong Wang; Kuiju Niu; Wenke Dong; Ran Zhang; Huiling Ma (Journal of Plant Physiology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Economical amidoxime-functionalized non-porous β-cyclodextrin polymer for selective detection and extraction of uranium - Yichen Sun; Ran Leng; Xinjie Ma; Jiangping Zhang; Bing Han; Guixia Zhao; Yuejie Ai; Baowei Hu; Zhuoyu Ji; Xiangke Wang (Chemical Engineering Journal, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Nanoscale chemomechanical variations of montmorillonite induced by the specificity of counterions—An in situ XRD and AFM study - Yingya Wang; Lingyu Ran; Lingya Ma; Runliang Zhu; Jingming Wei; Hongmei Liu; Yunfei Xi; Jianxi Zhu; Hongping He (Applied Clay Science, 2023)

Biosensor guided effective degradation of anti-nutritional factors via selected soybean fermentation process - Lizhou Ma; Ran Xun; Guohui Li; Yu Deng (Systems Microbiology and Biomanufacturing, 2023)

A novel microseismic classification model based on bimodal neurons in an artificial neural network - Chunchi Ma; Hang Zhang; Xiangqian Lu; Xiang Ji; Tianbin Li; Yong Fang; Wenjin Yan; Xuefeng Ran (Tunnelling and Underground Space Technology, 2023)

CO2 dynamics in a small and old subtropical reservoir in East Asia: Environmental controls driving seasonal and spatial variability - Chun Ngai Chan; Matthew J. Bogard; Fong Ching Ma; Yu Ching Ip; Boyi Liu; Shuai Chen; Lishan Ran (Science of The Total Environment, 2023)

Linear polygonal faults initiated Gully system around the margin slope of middle Miocene carbonate platform in the Northwest South China sea - Yintao Lu; Weimin Ran; Xiaoyong Xu; Xiwu Luan; Guozhang Fan; Taotao Yang; Hongxia Ma; Yun Yang; Li Li; Zhili Yang (Marine and Petroleum Geology, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Elemental composition and microbial community differences between wastewater treatment plant effluent and local natural surface water: A Zhengzhou city study - Qianqian Lu; Ran Zhao; Qiming Li; Yu Ma; Jing Chen; Qi Yu; Dehua Zhao; Shuqing An (Journal of Environmental Management, 2023)

Innovative natural antimicrobial natamycin incorporated titanium dioxide (nano-TiO2)/ poly (butylene adipate-co-terephthalate) (PBAT) /poly (lactic acid) (PLA) biodegradable active film (NTP@PLA) and application in grape preservation - Yanli Zheng; Xiaoyu Jia; Zhiyong Zhao; Yalin Ran; Meijun Du; Haiyu Ji; Yanfang Pan; Ziqin Li; Xiaowei Ma; Yue Liu; Lihua Duan; Xihong Li (Food Chemistry, 2023)

Effect of supercritical carbon dioxide on bacterial community, volatile profiles and quality changes during storage of Mongolian cheese - Jing Feng; Yuanrong Zheng; Xin Zhang; Ran Zhou; Ming Ma (Food Control, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

Sulfadiazine oxidation by peroxodisulfate and cobalt loaded graphitic biochar system: The dominant role of graphitic domain - Qiuhui Zhu; Kaixuan Guo; Shuanglong Ma; Shulian Wang; Xiaodan Tang; Ran Duan; Yan Huang; Jingzhen Wang; Gong Cheng; Shengjun Xu; Xuliang Zhuang (Chemical Engineering Journal, 2023)

Rational design of Lewis acid-base bifunctional nanopolymers with high performance on CO2/epoxide cycloaddition without a cocatalyst - Wenwen Zhang; Ran Ping; Xueyu Lu; Huibing Shi; Fusheng Liu; Jingjing Ma; Mengshuai Liu (Chemical Engineering Journal, 2023)

Cultivation of Haematococcus pluvialis in source-separated urine for biomass production and astaxanthin accumulation - Guan-qiu Ma; Li-hua Li; Yu Hong; Ming-ran Yu (Algal Research, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Mercury contamination in the riparian ecosystem during the reservoir discharging regulated by a mega dam - Yaseen Mir; Shengjun Wu; Maohua Ma; Yiguo Ran; Kai Zhu; Chirangano Mangwandi; Zakaria Ahmed Mirza (Environmental Geochemistry and Health, 2022)

The preparation of dodecyl trimethyl ammonium bromide modified titanium dioxide for the removal of uranium - Jian Wang; Ran Ma; Zheng Jiang (Environmental Science and Pollution Research, 2022)

Flowering characteristics and mating system of Fritillaria cirrhosa (Liliaceae), an endangered plant in China - Yanzhu Ma; Zhijia Cui; Chun Ya Cheng; Ran Li; Haixu Wu; Ling Jin; Yi Ma; Zhenheng Wang (Brazilian Journal of Botany, 2022)

Endovascular Therapy for Symptomatic Intracranial Artery Stenosis: a Systematic Review and Network Meta-analysis - Tao Wang; Kun Yang; Xiao Zhang; Jichang Luo; Ran Xu; Xue Wang; Yutong Yang; Xuesong Bai; Yan Ma; Yuxiang Yan; Liqun Jiao (Translational Stroke Research, 2022)

The association between air pollution, meteorological factors, and daily outpatient visits for urticaria in Shijiazhuang, Hebei Province, China: a time series analysis - Yaxiong Nie; Lijuan Liu; Shilin Xue; Lina Yan; Ning Ma; Xuehui Liu; Ran Liu; Xue Wang; Yameng Wang; Xinzhu Zhang; Xiaolin Zhang (Environmental Science and Pollution Research, 2022)

Flooding alleviates copper stress on Salix: Evidence from stoichiometric patterns among plant tissues - Yini Cao; Chuanxin Ma; Ran Tong; Jie Chen; Xiaogang Li; Guangcai Chen (Plant and Soil, 2022)

Parkinson’s Disease and Ischemic Stroke: a Bidirectional Mendelian Randomization Study - Shiyuan Fang; Xinzhi Hu; Tao Wang; Yutong Yang; Ran Xu; Xiao Zhang; Jichang Luo; Yan Ma; Aman B. Patel; Adam A. Dmytriw; Liqun Jiao (Translational Stroke Research, 2022)

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields - Huiyuan Xu; Han Sun; Jiajin Dong; Chengxue Ma; Jingxue Li; Zhuochun Li; Yihuan Wang; Junqi Ji; Xinrong Hu; Meihui Wu; Chunhua Zhao; Ran Qin; et al. (Theoretical and Applied Genetics, 2022)

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

Long non‑coding RNA PART1: dual role in cancer - Rui Ran; Chao-Yang Gong; Zhi-Qiang Wang; Wen-Ming Zhou; Shun-Bai Zhang; Yong-Qiang Shi; Chun-Wei Ma; Hai-Hong Zhang (Human Cell, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Two new chemical constituents from the rhizomes of Actaea dahurica - Sen-Ju Ma; Hai-Bo Li; Jun-Ran Shao; Qian-Qian Pang; Ting Li; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

A large-region fog detection algorithm at dawn and dusk for high-frequency Himawari-8 satellite data - Huiyun Ma; Yanan Li; Xiaojing Wu; Huihui Feng; Yinze Ran; Bingbo Jiang; Wei Wang (International Journal of Remote Sensing, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Effects of temperature and PM2.5 on the incidence of hand, foot, and mouth in a heavily polluted area, Shijiazhuang, China - Ran Liu; Jianning Cai; Weiheng Guo; Wei Guo; Wenjuan Wang; Lina Yan; Ning Ma; Xiaolin Zhang; Shiyong Zhang (Environmental Science and Pollution Research, 2022)

Seepage field distribution and water inflow laws of tunnels in water-rich regions - Zheng Li; Zi-quan Chen; Chuan He; Chun-chi Ma; Chao-ran Duan (Journal of Mountain Science, 2022)

International trade, CO2 emissions, and re-examination of “Pollution Haven Hypothesis” in China - Ran Wu; Tao Ma; Dongxu Chen; Wenxi Zhang (Environmental Science and Pollution Research, 2022)

Neural responses to rapidly selecting color names with different novelty - Hanqing Ma; Yunyi Zhang; Jingyi Zhang; Yong Liu; Zhiliang Long; Huangyanqiu Ran; Jingwen Li; Yingmei Qin; Jia Zhao (Cognitive Neurodynamics, 2021)

Lactate anions participate in T cell cytokine production and function - Jing Wen; Shipeng Cheng; Yaguang Zhang; Ran Wang; Jiefang Xu; Zhiyang Ling; Liyan Ma; Xinghao Ai; Bing Sun (Science China Life Sciences, 2021)

In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Tong Liu; Shijun Yu; Xiaoshan Zhu; Ran Liao; Zepeng Zhuo; Yanping He; Hui Ma (Frontiers in Marine Science, 2021)
Microplastics (MPs) have become the widespread contaminants, which raises concerns on their ecological hazards. In-situ detection of MP in water bodies is essential for clear assessment of the ecological risks of MPs. The present study proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantage of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene (PS) spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. It can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.

Terrestrial carbon cycle model-data fusion: Progress and challenges - Xin Li; Hanqing Ma; Youhua Ran; Xufeng Wang; Gaofeng Zhu; Feng Liu; Honglin He; Zhen Zhang; Chunlin Huang (Science China Earth Sciences, 2021)

Interactions between commensal bacteria and viral infection: insights for viral disease control in farmed animals - Chao Ran; Yu Li; Xufa Ma; Yadong Xie; Mingxu Xie; Yuting Zhang; Wei Zhou; Yalin Yang; Zhen Zhang; Li Zhou; Kaijian Wei; Zhigang Zhou (Science China Life Sciences, 2021)

Influence of Rahnella aquatilis on arsenic accumulation by Vallisneria natans (Lour.) Hara for the phytoremediation of arsenic-contaminated water - Guoliang Chen; Yanlin Ran; Yongqing Ma; Zhang Chen; Zhixian Li; Yuanqi Chen (Environmental Science and Pollution Research, 2021)

First complete mitogenomes of three mayflies in the genus Afronurus (Ephemeroptera: Heptageniidae) and their implications for phylogenetic reconstruction - Ran Li; Wei Zhang; Zhenxing Ma; Changfa Zhou (Biologia, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Screening beneficial bacteriostatic lactic acid bacteria in the intestine and studies of bacteriostatic substances - Zhijing Liu; Cong Xu; Ran Tian; Wan Wang; Jiage Ma; Liya Gu; Fei Liu; Zhanmei Jiang; Juncai Hou (Journal of Zhejiang University-SCIENCE B, 2021)

Precise orbit determination of BDS-3 satellites using B1C and B2a dual-frequency measurements - Ran Li; Ningbo Wang; Zishen Li; Yang Zhang; Zhiyu Wang; Hongyang Ma (GPS Solutions, 2021)

Correction to: FACS‑iChip: a high‑efficiency iChip system for microbial ‘dark matter’ mining - Haoze Liu; Ran Xue; Yiling Wang; Erinne Stirling; Shudi Ye; Jianming Xu; Bin Ma (Marine Life Science & Technology, 2021)

FACS-iChip: a high-efficiency iChip system for microbial ‘dark matter’ mining - Haoze Liu; Ran Xue; Yiling Wang; Erinne Stirling; Shudi Ye; Jianming Xu; Bin Ma (Marine Life Science & Technology, 2021)

Recent developments of doped g-C 3 N 4 photocatalysts for the degradation of organic pollutants - Xiaolu Liu; Ran Ma; Li Zhuang; Baowei Hu; Jianrong Chen; Xiaoyan Liu; Xiangke Wang (Critical Reviews in Environmental Science and Technology, 2021)

NO oxidation performance and kinetics analysis of BaMO3 (M=Mn, Co) perovskite catalysts - Ran Ao; Liping Ma; Zhiying Guo; Jing Yang; Liusen Mu; Jie Yang; Yi Wei (Environmental Science and Pollution Research, 2021)

Texture and Quality Assessment of Ready-to-eat Farmed Obscure Puffer Fish ( Takifugu obscurus ) Fillet by Evaluating Bacterial and Myofibrillar Degradation and Biochemical Changes during Refrigerated Storage - Ran Zhou; Yuanrong Zheng; Yuan Liu; Ming Ma (Journal of Aquatic Food Product Technology, 2020)

Characterization of phosphorus engineered biochar and its impact on immobilization of Cd and Pb from smelting contaminated soils - Jing Ren; Zixuan Zhao; Amjad Ali; Weidou Guan; Ran Xiao; Jim J. Wang; Sirui Ma; Di Guo; Baoyue Zhou; Zengqiang Zhang; Ronghua Li (Journal of Soils and Sediments, 2020)

Combining DC-GAN with ResNet for blood cell image classification - Li Ma; Renjun Shuai; Xuming Ran; Wenjia Liu; Chao Ye (Medical & Biological Engineering & Computing, 2020)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

Grenville-age orogenic event along the northeastern margin of the Quanji massif, NW China: constraints from ~1.1 Ga migmatite - Zhouxuan Xiao; Licheng Ma; Wan Jiang; Ran Wang; Yuyan Yao; Jie Cai; Jingyu Lin; Lu Li (Geosciences Journal, 2020)

Herbaceous layer determines the relationship between soil respiration and photosynthesis in a shrub-dominated desert plant community - Jie Ma; Ran Liu; Chenhua Li; Lianlian Fan; Guiqing Xu; Yan Li (Plant and Soil, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Comparative adsorption capabilities of rubbish tissue paper–derived carbon-doped MgO and CaCO3 for EBT and U(VI), studied by batch, spectroscopy and DFT calculations - Ayub Khan; Dongli Wei; Fazli Khuda; Ran Ma; Muhammad Ismail; Yuejie Ai (Environmental Science and Pollution Research, 2020)

Membrane fouling control by Ca2+ during coagulation–ultrafiltration process for algal-rich water treatment - Cong Ma; Jingyun Huang; Yulan Wang; Liang Wang; Hongwei Zhang; Zhilin Ran; Jeffrey R. McCutcheon (Environmental Geochemistry and Health, 2020)

Comparative transcriptome analyses provide insights into the adaptation mechanisms to acute salt stresses in juvenile Sinonovacula constricta - Bin Ma; Zhaoshou Ran; Xiaorong Xu; Jilin Xu; Kai Liao; Jiayi Cao; Xiaojun Yan (Genes & Genomics, 2019)

Effects of different green manure treatments on soil apparent N and P balance under a 34-year double-rice cropping system - Xi Hong; Chao Ma; Jusheng Gao; Shiming Su; Tao Li; Zunchang Luo; Ran Duan; Yanan Wang; Lingyu Bai; Xibai Zeng (Journal of Soils and Sediments, 2019)

Removal of low-concentration thiophene by DC corona discharge plasma - Xueqian Wang; Mengxue Guo; Ran Zhang; Ping Ning; Yixing Ma; Qiang Ma; Langlang Wang (Environmental Science and Pollution Research, 2019)

Partitioning water source and sinking process of a groundwater-dependent desert plant community - Ran Liu; Yugang Wang; Congjuan Li; Jie Ma; Yan Li (Plant and Soil, 2018)

Energy savings evaluation in public building sector during the 10th–12th FYP periods of China: an extended LMDI model approach - Minda Ma; Ran Yan; Weiguang Cai (Natural Hazards, 2018)

Cumulative effects of cascade hydropower stations on total dissolved gas supersaturation - Qian Ma; Ran Li; Jingjie Feng; Jingying Lu; Qin Zhou (Environmental Science and Pollution Research, 2018)

Graphene oxide-coated stir bar sorptive extraction of trace aflatoxins from soy milk followed by high performance liquid chromatography-laser-induced fluorescence detection - Haiyan Ma; Congcong Ran; Mengjiao Li; Jinglin Gao; Xinyu Wang; Lina Zhang; Jing Bian; Junmei Li; Ye Jiang (Food Additives & Contaminants: Part A, 2018)

Performance of GPS and GPS/SINS navigation in the CE-5T1 skip re-entry mission - Meng Wang; Tao Shan; Lin Ma; Ran Tao; Chunliang Chen (GPS Solutions, 2018)

An extended STIRPAT model-based methodology for evaluating the driving forces affecting carbon emissions in existing public building sector: evidence from China in 2000–2015 - Minda Ma; Ran Yan; Weiguang Cai (Natural Hazards, 2017)

Thermal ecology of three coexistent desert lizards: Implications for habitat divergence and thermal vulnerability - Shu-Ran Li; Yang Wang; Liang Ma; Zhi-Gao Zeng; Jun-Huai Bi; Wei-Guo Du (Journal of Comparative Physiology B, 2017)

A STIRPAT model-based methodology for calculating energy savings in China’s existing civil buildings from 2001 to 2015 - Minda Ma; Ran Yan; Weiguang Cai (Natural Hazards, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Precipitation Pattern Determines the Inter-annual Variation of Herbaceous Layer and Carbon Fluxes in a Phreatophyte-Dominated Desert Ecosystem - Ran Liu; Ellen Cieraad; Yan Li; Jie Ma (Ecosystems, 2016)

Intracellular Ca2+ and related proteins in patients with oral lichen planus - Jiang-Min Ma; Ran Wang; Juan-Yong Xu; Yuan Fan (Immunologic Research, 2016)

A high frequency of allopolyploid speciation in the gymnospermous genus E phedra and its possible association with some biological and ecological features - Hui Wu; Zhen Ma; Ming‐Ming Wang; Ai‐Li Qin; Jin‐Hua Ran; Xiao‐Quan Wang (Molecular Ecology, 2016)
The origin and evolution of polyploids have been studied extensively in angiosperms and ferns but very rarely in gymnosperms. With the exception of three species of conifers, all natural polyploid species of gymnosperms belong to Ephedra , in which more than half of the species show polyploid cytotypes. Here, we investigated the origin and evolution of polyploids of Ephedra distributed in the Qinghai–Tibetan Plateau ( QTP ) and neighbouring areas. Flow cytometry ( FCM ) was used to measure the ploidy levels of the sampled species that are represented by multiple individuals from different populations, and then, two single‐copy nuclear genes ( LFY and DDB 2) and two chloroplast DNA fragments were used to unravel the possible origins and maternal donors of the polyploids. The results indicate that the studied polyploid species are allopolyploids, and suggest that allotetraploidy is a dominant mode of speciation in Ephedra . The high percentage of polyploids in the genus could be related to some of its biological attributes such as vegetative propagation, a relatively high rate of unreduced gamete formation, and a small genome size relative to most other gymnosperms. Significant ecological divergences between allotetraploids and their putative progenitors were detected by PCA s and anova and Tukey's tests, with the exception of E. saxatilis . The overlap of geographical distributions and ecological niches of some diploid species could have provided opportunities for interspecific hybridization and allopolyploid speciation.

Pharmacodynamics and Pharmacokinetics of Levobupivacaine Used for Epidural Anesthesia in Patients with Liver Dysfunction - Juhong Ran; Yanping Wang; Fangkun Li; Wei Zhang; Minyu Ma (Cell Biochemistry and Biophysics, 2015)

Feeding Postures of Cao Vit Gibbons (Nomascus nasutus) Living in a Low-Canopy Karst Forest - Hanlan Fei; Changyong Ma; Thad Q. Bartlett; Ran Dai; Wen Xiao; Pengfei Fan (International Journal of Primatology, 2015)

Effectiveness of an Eco-friendly Polymer Composite Sand-Fixing Agent on Sand Fixation - Guofu Ma; Feitian Ran; Enke Feng; Zhibao Dong; Ziqiang Lei (Water, Air, & Soil Pollution, 2015)

Biochemical characterization of caffeoyl coenzyme A 3-O-methyltransferase from wheat - Qing-Hu Ma; Hao-Ran Luo (Planta, 2015)

Molecular Interactions of Flavonoids to Hyaluronidase: Insights from Spectroscopic and Molecular Modeling Studies - Hua-jin Zeng; Jiao Ma; Ran Yang; You Jing; Ling-bo Qu (Journal of Fluorescence, 2015)

Swine PPAR-γ2 expression upregulated in skeletal muscle of transgenic mice via the swine Myozenin-1 gene promoter - Juanjuan Ma; Jin Chai; Yangyang Shang; Yujiao Li; Ran Chen; Jia Jia; Siwen Jiang; Jian Peng (Transgenic Research, 2015)

Scaffold-based design of xanthine as highly potent inhibitors of DPP-IV for improving glucose homeostasis in DIO mice - Yan Ran; Heying Pei; Caifeng Xie; Liang Ma; Yuzhe Wu; Kai Lei; Mingfeng Shao; Minghai Tang; Mingli Xiang; Aihua Peng; Yuquan Wei; Lijuan Chen (Molecular Diversity, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Polycyclic aromatic hydrocarbon (PAH) exposure and oxidative stress for a rural population from the North China Plain - Qiaoyun Yang; Xinghua Qiu; Ran Li; Jin Ma; Keqiu Li; Guang Li (Environmental Science and Pollution Research, 2015)

A Combinatorial Yeast Overlay Method for the Isolation of Antibacterial Oligopeptides - Ran He; Liang Cui; Yan Cao; Zhixue Wang; Kai Wang; Min Fu; Shaoyun Song; Chuanfu Dong; Xiaoxuan Wu; Ye Gao; Xiaoxiao Zhang; Fan Feng; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Response of the bacterial diversity and soil enzyme activity in particle-size fractions of Mollisol after different fertilization in a long-term experiment - Ning Ling; Yuming Sun; Jinghua Ma; Junjie Guo; Ping Zhu; Chang Peng; Guanghui Yu; Wei Ran; Shiwei Guo; Qirong Shen (Biology and Fertility of Soils, 2014)

Atg5 regulates late endosome and lysosome biogenesis - JunYa Peng; Ran Zhang; YiTong Cui; HaoDong Liu; XiaoXin Zhao; Lei Huang; MingXu Hu; XiaoXi Yuan; BenYu Ma; XiaoWei Ma; Ueno Takashi; Komatsu Masaaki; et al. (Science China Life Sciences, 2014)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Dissipation and Residue Determination of Fluoroglycofen-Ethyl in Soybean and Soil by UPLC-MS–MS - Yue Geng; Ran Jia; Chongjiu Li; Xiaodong Ma; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Transient Focal Cerebral Ischemia Induces Long-term Cerebral Vasculature Dysfunction in a Rodent Experimental Stroke Model - Ali Winters; Jessica C. Taylor; Ming Ren; Rong Ma; Ran Liu; Shao-Hua Yang (Translational Stroke Research, 2012)

Polymorphisms of KiSS-1 and GPR54 genes and their relationships with litter size in sheep - Mingxing Chu; Chaoting Xiao; Tao Feng; Yan Fu; Guiling Cao; Li Fang; Ran Di; Qianqian Tang; Dongwei Huang; Yuehui Ma; Kui Li; Ning Li (Molecular Biology Reports, 2012)

NAD(P)H oxidase inhibiting with apocynin improved vascular reactivity in tail-suspended hindlimb unweighting rat - Ran Zhang; Hai-hong Ran; Jin Ma; Yun-gang Bai; Le-jian Lin (Journal of Physiology and Biochemistry, 2012)

Polymorphisms of coding region of BMPR-IB gene and their relationship with litter size in sheep - Mingxing Chu; Lihua Jia; Yingjie Zhang; Mei Jin; Hongquan Chen; Li Fang; Ran Di; Guiling Cao; Tao Feng; Qianqian Tang; Yuehui Ma; Kui Li (Molecular Biology Reports, 2011)

Experimental research on the seismic behavior of CSPSWs connected to frame beams - Lanhui Guo; Xinbo Ma; Ran Li; Sumei Zhang (Earthquake Engineering and Engineering Vibration, 2011)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

Occurrence and environmental risk of endocrine-disrupting chemicals in surface waters of the Pearl River, South China - Jian Gong; Yong Ran; Diyun Chen; Yu Yang; Xiaoxuan Ma (Environmental Monitoring and Assessment, 2009)

Concentrations and inventories of polycyclic aromatic hydrocarbons and organochlorine pesticides in watershed soils in the Pearl River Delta, China - Xiaoxuan Ma; Yong Ran; Jian Gong; Mengyao Zou (Environmental Monitoring and Assessment, 2008)

Cloning, Sequencing, and Characterization of the Azospirillum brasilense fhuE Gene - Yanhua Cui; Ran Tu; Yue Guan; Luyan Ma; Sanfeng Chen (Current Microbiology, 2006)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)

Differential expression of glucose-regulated protein 78 during spermatogenesis - Ran Huo; Ye-fei Zhu; Xiang Ma; Min Lin; Zuo-min Zhou; Jia-hao Sha (Cell and Tissue Research, 2004)